Effects of sampling strategy, geographical origin, and soil on stable isotopes and multi-elements for the traceability of Chinese PGI oranges - Jiahui Wu; Hao Deng; Guang Wu; Hanyi Mei; Karyne M. Rogers; Yurong Huang; Shengzhi Shao; Chunlin Li; Ping Wang; Jing Nie; Yuwei Yuan; Yongzhi Zhang (Food Control, 2026)

AIE-active photoresponsive Ir(III) complex as an oxidase mimic for ratiometric ascorbic acid detection - Qianghui Zheng; Ping Huang; Ying Peng; Mei-Jin Li; Fengfu Fu (Analytica Chimica Acta, 2026)

Aspergthones A and B, hybrids of dehydrosterigmatocystin with phenolic derivatives, isolated from the endophytic fungus Aspergillus versicolor VDL117 - Shan Hu; Mei Yang; Zhi-Yu Zhang; Yun-Xian Li; Xiao-Qin Yang; Wei-Hua Wang; Ying-Jun Zhang; Ping Zhao; Guo-Lei Zhu (Phytochemistry Letters, 2026)

Foraminiferal composition of the early Oligocene Globigerinid-rich limestone in the Baiyun Sag, Pearl River Mouth Basin, and its paleo-environmental significance - Guang-Rong Peng; Cui Shi; Xiao-Ping Li; Xin-Yu Liu; Le-Yi Xu; Kai Zhang; Qi-Mei Guo; Bao-Hua Li (Palaeoworld, 2026)

Tracking sedimentation process under progressive mangrove propagation in low-energy bays - Weiming Li; Zhijun Dai; Xuefei Mei; Jiejun Luo; Wenjun Zeng; Ping Zhang; Ran Chen; Jinping Cheng (Marine Geology, 2026)

Enhanced solar-driven interfacial vapor generation of lignite-based aerogel via water and thermal dual management - Mei Xiong; Hong-Lei Yan; Zhan-Ku Li; Wei-Dong Zhang; Jing-Chong Yan; Zhi-Ping Lei; Zhao Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui (Journal of Environmental Chemical Engineering, 2026)

GABA-enriched Lactobacillus buchneri XBMU-C1 fermentation broth lowers blood pressure in L-NAME-induced hypertensive rats via RAAS suppression and PI3K/Akt/eNOS activation - Dandan Gao; Chenchen Wang; Ying Chen; Jiwen Wang; Junyao Mei; Yujie Cao; Xuankang Yang; Shangyun Kang; Jinyong Ma; Ping Li (Food Research International, 2026)

Isotopic compositions reveal distinct roles of in-cloud and below-cloud scavenging in dissolved and particulate mercury in precipitation - Zixuan Wang; Tao Li; Hongming Cai; Mei Meng; Jiubin Chen; Lin Du; Jiebo Zhen; Ping Du; Yan Wang (Atmospheric Environment, 2026)

Mapping the True 3D Architecture: Quantitative Morphological Diversity of Human Hepatic Functional Unit Revealed by Fluorescence Micro-optical Section Tomography - Na Chen; Hongjun Liu; Xiaofeng Mei; Silin Liu; Hongjia Hu; Yunxi Lv; Qi Li; Wei Feng; Yifang Ping; Lu Zheng; Shiwu Dong; Yi Wu (Tissue and Cell, 2026)

Advancing startup control procedures for enhanced reduction of persistent organic pollutant emissions from municipal solid waste incinerators - Nicholas Kiprotich Cheruiyot; Cindy Soo Yun Tan; Hsi-Hsien Yang; Kuan-Hsien Li; Syeda Seemab Naqvi; Mei-Jou Lu; Guo-Ping Chang-Chien; Lin-Chi Wang (Waste Management, 2026)

Isoprenylated phenolic derivatives from Corethrodendron scoparium and their anti-triple negative breast cancer activity - Yuan Gao; Ping Hai; Hai-Yan Jia; Mei-Ling Yang; Hui-Xia Fan; Jin Yang; Xian-Yan Li; Lian Yang; Zhi-Qiang Luo; Jian Yang (Phytochemistry, 2026)

Comparison of food allergic immune responses in sensitized female and male Balb/c mouse induced by Lateolabrax japonicus tropomyosin - Meng-Si Li; Qing-Mei Liu; Fei Xia; Li-Qiang Zhong; Zhi-Qiang Chen; Ya-Ping Wu; Yu-Ni Liao; Gui-Xia Chen; Yi-Xiang Liu; Guang-Ming Liu (Food and Chemical Toxicology, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Synthesis and biological evaluation of Phorbazole D analogues identify IO-5a as a promoter of hUC-MSC chondrogenic differentiation - Ai-zhu Wang; Xiao-mei Liu; Li-ming Zhang; Lu-lu Fu; Ping Li; Jie-ping Zhang; Hua Han (Molecular Diversity, 2026)

Linking the dietary inflammation index to sarcopenia in diabetes: mediation by body roundness index and evidence from complementary analyses - Yang Yang; Ren-hua Lv; Peng-min Liu; Yan-qiu Sun; Lu-ping Wang; Yu Yu; Li-mei Zhang; Xin-yang Zhang (European Journal of Applied Physiology, 2026)

Differential effects of a novel mesoionic insecticide, triflumezopyrim, on Apis mellifera and Apis cerana - Mei-Ling Zhang; Shu-Wei Wang; Wen-Min Li; Sasiprapa Krongdang; Yan-Yan Wu; Ping-Li Dai; Shan-Shan Li; Jing Gao (Journal of Hazardous Materials, 2026)

Supplementing with vitamin B6 during the active phase can promote digestion, enhance intestinal barrier integrity, and accelerate the maturation of ileum flora in juvenile mice - Ya-Xin Liu; Jin-Hao Pang; Li-Ping Chen; Fei Huan; Qing-Mei Liu; Meng Liu; Yan-Ling Hao; Chen-Hong Zhang; Lian-Zhong Luo; Guang-Ming Liu (Food Bioscience, 2026)

Phase evolution matters: How Fe(II) reshapes coprecipitate surfaces for enhanced U(VI) adsorption - Chaofei Zhang; Yuan Chen; Huiyang Mei; Weichao Zhang; Beihang Zhang; Wentao Zhang; Ping Li; Zhenying Lv; Jianjun Liang; Qiaohui Fan (Water Research, 2026)

First fossil fruit of Spatholobus (Papilionoideae, Fabaceae) from East Asia - Yi-Shan Zhao; Zhen-Dong Cao; Jing-Nan Huang; Zi-Yi Li; Torsten Wappler; Zhen-Xian Zhang; Shu-mei Xiao; Wei-Yu-Dong Deng; San-Ping Xie (Review of Palaeobotany and Palynology, 2026)

Formation process of Fe-Mn Co-precipitates and Its implications for U(VI) immobilization: Mechanisms and environmental factors - Zhenying Lv; Huiyang Mei; Beihang Zhang; Weichao Zhang; Ping Li; Chaofei Zhang; Jianjun Liang; Qiaohui Fan (Journal of Environmental Chemical Engineering, 2026)

Mg–K isotopic compositions deciphering mantle heterogeneity beneath southeast Tibet - Qiong Chen; Hao Cheng; Guo-Chun Zhao; Mei-Fu Zhou; Ping-Ping Liu; Wen-Jun Li; Min Sun (Geochimica et Cosmochimica Acta, 2026)

Corrigendum to “Hellebrigenin induces cell cycle arrest and apoptosis in human hepatocellular carcinoma HepG2 cells through inhibition of Akt” [Chemico. Biol. Interact. 219 (2014) 184-194] - Li-Juan Deng; Li-Ping Hu; Qun-Long Peng; Xiao-Lin Yang; Liang-Liang Bai; Anita Yiu; Yong Li; Hai-Yan Tian; Wen-Cai Ye; Dong-Mei Zhang (Chemico-Biological Interactions, 2026)

Shorter to be effective: subanesthetic-dose ketamine infusion reduces the global and regional path length of brain functional connectivity in patients with treatment-resistant depression and suicidal ideation - Wei-Chen Lin; Li-Kai Cheng; Tung-Ping Su; Li-Fen Chen; Pei-Chi Tu; Cheng-Ta Li; Ya-Mei Bai; Shih-Jen Tsai; Mu-Hong Chen (Psychopharmacology, 2026)

Dual-metal sites synergy in Fe/V-N-C catalyst: Boosting ECL signals for ultrasensitive detection of aflatoxin B1 in corn and peanut - Ping Yuan; Ai-Jun Wang; Li-Ping Mei; Yacheng Shi; Pei-Xin Yuan; Jiu-Ju Feng (Food Chemistry, 2026)

A critical review on abiotic geologic hydrogen generation: Mechanisms and controls - Qingxia Zheng; Ruibo Wu; Ping Li; Zhe Ding; Wentao Zhang; Huiyang Mei; Weichao Zhang; Jianjun Liang; Qiaohui Fan (Earth-Science Reviews, 2026)

Engineering of Azotobacter chroococcum enables potential replacement of synthetic nitrogen fertilizer and mitigation of nitrogen pollutants release under medium-fertility field conditions - Ping Tian; Jun-Feng Wang; Dao-Yuan Wang; Yu-Dian Xun; Xiao-Hui Shi; Ming-Zhu Chen; Yun-Ying Liang; Mei-Ting Yang; Qu-Sheng Li (Bioresource Technology, 2026)

Occurrence, ecological risk, and human health assessment of herbicide residues in Chaohu Lake, China - Yong-mei Zhang; Ping-ping Fan; Ling-zhi Zhang; Wei Yu; Song Xia; Fa-li Liu; Xue-de Li (Journal of Environmental Chemical Engineering, 2026)

Construction of CoTiO3/CdS catalysts in-situ grown on recyclable chitosan hydrogel beads and their application in photocatalytic hydrogen evolution from water splitting - Meijuan Ding; Mei Li; Qingyang Yu; Ziyu Li; Jingyi Nie; Aohui Ping; Chaoqi Ding; Hongbo Li; Bing Yang; Zhiliang Jin (Journal of Environmental Chemical Engineering, 2026)

Pseudosparassis yunnanensis, gen. et sp. nov. (Sclerotiniaceae, Helotiales, Ascomycota) from Yunnan Province, Southwestern China - Yuan-Hao Ma; Qi Zhao; Li-Mei Huang; Ping Liu; Hong-Mei Chai; Yong-Chang Zhao; Hong-Li Su; Ishika Bera; Wei-Min Chen (Mycological Progress, 2026)

Breaking the antimicrobial resistance dilemma: marine natural products, a treasure trove for the development of new anti-Staphylococcus aureus drugs - Peng-Jie Li; Liu-Xia Lv; Xi-Zhen Cao; Jian-Yu Liu; Ji-Xiu Gao; Hao-Ran Li; Gulab Said; Dan Chen; Bo Yao; Xin Liu; Mei-Yan Wei; Xiao-Ping Yang; et al. (Marine Life Science & Technology, 2026)
Antimicrobial resistance (AMR) affects multiple fields, including medicine, pharmacy, food safety, and animal husbandry, and poses a major threat to public health and economic development. Staphylococcus aureus has emerged as one of the most critical bacterial pathogens due to its widespread prevalence and significant genetic plasticity. This review outlines currently approved small-molecule drugs for clinical use and their mechanisms in controlling bacterial infections and antimicrobial resistance, highlighting the development of novel agents as an effective strategy to combat AMR. Special emphasis is placed on the antibacterial activity of marine-derived natural products (MNPs) against S. aureus , and a systematic analysis is presented for the first time on the structures, origins, activities, and structure–activity relationships of 1,192 compounds reported in 468 publications from 1977 to 2025. Among these, 36 MNPs exhibited significant activity against both methicillin-sensitive S. aureus and methicillin-resistant S. aureus (MIC ≤ 1 µg/mL). Macrolides and peptides represented the most prevalent structural classes, with compounds displaying potent activity accounting for 24% and 27% of the total active compounds, respectively. Further drug-likeness analysis shows that MNPs have promising therapeutic potential. Among the 160 highly active MNPs, over 80% have suitable lipid-water partition coefficients, and 41% fully meet Lipinski's Rule of Five. Structural analysis reveals tetrahydrofuran, tetrahydropyran, and sugar units as the most common motifs, present in 20, 16, and 14 compounds, respectively. Technologies and strategies to accelerate the development of marine-derived antibacterial drugs are also proposed. This will serve stakeholders across diverse sectors by supporting cross-sectoral coordination to address AMR.

Process parameter optimization for greenhouse gas mitigation during green-waste composting and mechanistic insights from microbe–environment networks in treatments with contrasting outcomes - Xiaowen Li; Min Cao; Wenyuxin Huang; Hao Mei; Pan Luo; Ping Ma; Junhao Zhang; Weiqin Zhu; Miaomiao He; Ying Ding (Journal of Cleaner Production, 2026)

Mechanistic investigations into cytochrome c-U(VI) adsorption-reduction on ferrihydrite: Implications for subsurface microbial U redox under anaerobic conditions - Jiayu Song; Huiyang Mei; Xiangxian Ma; Ghufran Uddin; Jianjun Liang; Ping Li; Weichao Zhang; Qiaohui Fan (Journal of Environmental Chemical Engineering, 2026)

Defect passivation with Pb for high-performance Sb2S3 solar cells via vapor transport deposition - Gan Huang; Xin-Yi Cai; Hu Li; Jin-Rui Cai; Ying-Sen Xia; Zhi-Ping Huang; Li-Mei Lin; Fu-Bao Gong; Shui-Yuan Chen; Gui-Lin Chen (Chemical Engineering Journal, 2026)

Eight new dammarane-type triterpenoid saponins from Gynostemma pentaphyllum - Gang Li; Guang Yang; Xiao-juan Chen; Peng-xin Lu; Hai-zhen Liang; Mei-yan Wang; Jie Zhang; Bao-lin Guo; Bai-ping Ma (Natural Product Research, 2026)

Environmental co-exposure to roxarsone and heavy metals drives bacterial antibiotic multidrug resistance via genetic and phenotypic adaptations - Qian-He Liu; Li Yuan; Zheng-Hao Li; Kenneth Mei Yee Leung; Guo-Ping Sheng (Water Research, 2026)

Pinoresinol diglucoside alleviates hindlimb unloading-induced bone loss in mice - Ying-Ying Xuan; Liang Li; Yi Wu; Zhen-Long Wei; Mei Zhang; Min-Na Liu; Dong-Shuai Shen; Yu-Hai Gao; Cory J Xian; Hui-Ping Ma; Ke-Ming Chen (Life Sciences in Space Research, 2026)

Effects of neutral and alkaline salt stress on seed germination, physiological and biochemical properties of Andrographis paniculata (Burm.f.) Wall. ex Nees - Ming Zhang; Kai-xuan Shi; Jia Jiang; Qiao-chu Ma; Wan-bo Ding; Qing-ni Peng; Ya-ping Shi; Mei-long Liu; Zhi Sun; Ming Li; Sheng Wang (Journal of Applied Research on Medicinal and Aromatic Plants, 2026)

Aboveground living plant-based methane production does not dominate methane emissions in terrestrial ecosystems - Zhi-Ping Wang; Luke C. Jeffrey; Josep Barba; Katerina Machacova; Xi-Mei Zhang; Ang Li; Shi-Jie Han (Planta, 2026)

Mechanical properties of monolithic EPS-coated lightweight soil: unconfined compressive strength and small-strain dynamic characterization - Ping Jiang; Xinghan Wu; Wei Wang; Na Li; Haihua Zhan; Guoxiong Mei; Jianfeng Wang (Soil Dynamics and Earthquake Engineering, 2025)

Microbial community assembly driven by dissolved organic matter and sulfate induces arsenic transformation in shallow aquifers of lateritic red soil regions - Ming-Zhu Chen; Jun-Feng Wang; Jian-Ping Ouyang; Yi-Rong Deng; Mei-Ting Yang; Yu-Dian Xun; Xiao-Hui Shi; Guang-Yong Tang; Jian-Ying Mo; Han-Jie Ye; Qu-Sheng Li (Journal of Hazardous Materials, 2025)

Wheat germ peptides enhance hypoxia tolerance by modulating gut microbiota and reprogramming brain energy metabolism in mice - Jing-yang Cai; Ying-Ying Liu; Meng-Cheng Li; Xin-Xin Guo; Ai-Mei Liao; Yin-Chen Hou; Quan-Ping Liu; Yong-Chao Fan; Long Pan; Ji-Hong Huang (Food Bioscience, 2025)

A high safety composite separator for powerful battery with ultra-long lifespan over 14,000 cycles at 10C - Ke Fang; Yan-yan Chen; Jian-wei Ji; Tian-kun Gao; Mei-qi Hu; Lian-li Zou; Ying Liu; Li-ping Zhou; Ming-quan Liu; Mao-xiang Jing (Chemical Engineering Journal, 2025)

Natural compound rhein-based bimetallic nanosheets to induce ferroptosis and activate STING pathway for enhanced cancer immunotherapy - Chang Li; Tiancheng Xie; Xilong Mei; Yu Wen; Mi Huang; Hu Guo; Ping Lu; Xiaoxin Yang; Jun Liu (Chemical Engineering Journal, 2025)

Mechanically robust and rapidly self-recovering hyaluronic acid-based conductive hydrogels via fully physical double-network crosslinking for sensitive strain sensors - Ye-Xiong Huang; Mei-Dan Luo; Dewei Ye; Jinmin Li; Ku Shu; Xian-Ping Chen; Kai Zheng (Chemical Engineering Journal, 2025)

Self-adaptive auditory perceptual system for voice instruction recognition powered by triboelectric acoustic sensor - Si Yuan Zhou; Shi Han Wang; Jing Zhang; Lin Feng Wu; Wei Sheng Wang; Bei Chen Gong; Jia Kang Di; Xiang Mei Duan; Hua Ping Wu; Li Qiang Zhu (Chemical Engineering Journal, 2025)

Inhibitory Effect of TrxR Inhibitor Ag (Ⅰ) Schiff Base Complex Against Cervical Cancer Via ROS-mediated ASK1/MAPK Signaling and Autophagy - Jian-Jun Liu; Jia-Hua Zou; Bin Dong; Xue-Ping Lu; Li-Feng Chen; San-Mei Ma; Zhong Liu (Biological Trace Element Research, 2025)

Multiscale responses of gap-graded soil under the combined effect of train vibration and seepage erosion - Dong-Mei Zhang; Hui-Hao Chen; Xiao-Chuang Xie; Si-Rui Chen; Zhao-Geng Chen; Jia-Ping Li (Transportation Geotechnics, 2025)

Improvement of RNAi efficiency by delivering of dsRNA formulated with cell-penetrating disulfide polymer in the fall Armyworm, Spodoptera frugiperda - Xu Wu; Wen-Mei Li; Qiang Xu; Xiao-Ping Yi; Da-He Zhang; Ming-Zhe He; Yu-Hong Ren (Journal of Insect Physiology, 2025)

Synergistic dual-Lewis sites in cobalt-doped Fe3S4 for enhanced hydrogen peroxide activation and contaminant degradation - Li-Ping Jin; Fan Zhou; Qin Liu; Su-Qin Wang; Meng-Meng Zeng; Xin-Yu Huang; Li Liu; Xiao-Han Yu; Mei-Feng Wu; Jian-Ping Zou (Chemical Engineering Journal, 2025)

Synergistic coupling of Pd@PtRh nanozyme with NiMn2O4/In2S3 Z-scheme heterojunction for ultrasensitive photoelectrochemical sensing of malathion - Rui-Jin Shao; Ke Yin; Lei Zhao; Yadong Xue; Ai-Jun Wang; Li-Ping Mei; Pei Song; Jiu-Ju Feng (Chemical Engineering Journal, 2025)

Fabrication of metal organic framework membranes via hierarchical metal-governed interfacial regulation synergy for efficient propylene/propane separation - Bing-Hong Chen; Yu-Jie Wang; Li-Hao Xu; Yan-Mei Zhang; Qian-Qian Li; Zhi-Ping Zhao (Chemical Engineering Journal, 2025)

Androgen induces 3′UTR shortening of de novo lipogenesis genes by alternative polyadenylation in prostate cancer cells - Wei-Jie Sun; Fei Liang; Hui Zhao; Yun-Mei Wang; Zhong-Yin Zhou; Hui Xu; Hang Liu; Dong Tang; An-Long Xu; Yong-Gui Fu; Xi Li; Jun Ouyang; et al. (Science China Life Sciences, 2025)
Alternative polyadenylation (APA) is a pervasive mechanism that is emerging as a formidable player in post-transcriptional regulation. The transcriptional landscape can be altered via APA in response to various stimulating factors. Using the PacBio single-molecule long-read sequencing method, we present for the first time the 3′UTR landscape and reveal a global increase of APA events in prostate cancer (PCa) LNCaP cells in response to androgen dihydrotestosterone (DHT), a critical regulator of PCa progression. With evidence from differential gene expression analyses of Illumina RNA-sequencing data, we demonstrated that genes with DHT-induced changes in both expression and APA were enriched in lipid metabolism. These genes predominantly supported de novo fatty acid synthesis, such as FASN and ACSL3 . Furthermore, we showed that an isoform switch to the proximal poly(A) site of these genes depended on the androgen receptor, and the expression of cancer-associated genes was upregulated by the escape of miRNA-regulated repression machinery. To address the role of key gene shortening in PCa, we prepared 22RV1-FS cells missing the distal poly(A) signal of FASN in the AR + PCa cell line 22RV1 using CRISPR/Cas9 technology. As expected, the edited 22RV1-FS cells overexpressed FASN mRNA and protein and were inclined to cell proliferation in vitro and tumorigenesis in vivo . Interestingly, we found that FASN transcripts with a shortened 3′UTR were significantly increased in advanced PCa and castration-resistant prostate cancer compared with benign prostate hyperplasia, suggesting a possible association between usage of the proximal poly(A) site and disease progression. Therefore, our study highlights the importance of the APA mechanism in response to DHT stimulation in PCa cells and provides a novel regulatory mechanism through which DHT-induced APA causes altered expression of de novo lipogenesis genes, with a possible association with the progression of PCa.

ZWINT down-regulated by miR-495-3p inhibited lung metastasis of breast cancer by blocking p38 MAPK signaling pathway activation - Ming-tao Shao; Wei-wen Li; Yong Li; Ping Chen; Shuai-shuai Yu; Wen-jie Lu; Chun-mei Chen; Yan Dong; Yi-wen Zhang; Qun-chen Zhang (Human Cell, 2025)
Breast cancer metastasis is the primary cause of patient mortality, yet effective therapeutic targets remain limited. Building on our prior identification of ZWINT as a prognostic marker linked to metastasis, this study defines its critical functional role and regulatory mechanism. Multi-omics analysis revealed a strong association between ZWINT expression and metastatic processes across breast cancer subtypes. Functionally, ZWINT knockdown significantly inhibited breast cancer cell migration and invasion in vitro and dramatically reduced lung metastasis in vivo. Mechanistically, we discovered that miR-495-3p directly targets and suppresses ZWINT expression, and this miR-495-3p/ZWINT axis acts through inhibiting p38 MAPK pathway activation to suppress metastatic progression in vitro. Our findings demonstrate that ZWINT drives breast cancer metastasis and is negatively regulated by miR-495-3p. The newly identified miR-495-3p/ZWINT/p38 MAPK axis may provide a promising therapeutic target for suppressing breast cancer progression.

Experimental research on citric acid modified magnesium oxysulfate cement composites under dry-wet cycles: Mechanical properties and microscopic mechanism - Na Li; Yifang Song; Wei Wang; Ping Jiang; Xinyu Yan; Jun Zhang; Guoxiong Mei (Sustainable Chemistry and Pharmacy, 2025)

Reducing melamine exposure and oxidative stress markers in melamine-exposed workers: A pragmatic intervention study - Chia-Fang Wu; Chih-Hong Pan; Yu-Ming Hsu; Chiung-Yu Peng; Ching-Mei Cheng; Sih-Syuan Li; Chien-Ping Huang; Ming-Tsang Wu (Journal of Hazardous Materials, 2025)

Rational design of CdS/Ce-UiO-66 heterostructure for high-efficiency photocatalytic oxidation of amines to imines - Huan Zhang; Cai-Yong Zhu; Wen-Qi Jin; Zi-Yu Li; Peng Li; Wei Gao; Ping Zhang; Xiu-Mei Zhang (Journal of Environmental Chemical Engineering, 2025)

High-entropy sulfide and nanozyme hybrid system with synergistic interface-engineering: Ultra-sensitive photoelectrochemical detection of chloramphenicol - Yi-Hong Chen; Ai-Jun Wang; Ya-Cheng Shi; Li-Ping Mei; Pei Song; Tiejun Zhao; Jiu- Ju Feng (Chemical Engineering Journal, 2025)

Unlocking the power of sesquiterpenoids: phytochemistry and bioactivities in Artemisia (2017–2023) - Li Ping Tang; Tao Liu; Xiao Yu Han; Bin Li; Hong Dong Liu; Xue Mei Gao (Phytochemistry Reviews, 2025)

Therapeutic effects of Scutellaria baicalensis total flavonoids on metabolic syndrome in rats via modulation of PPARα and PPARγ signaling - Yang Zhou; Zhi-Ping Li; Yu-Hang Lian; Xin Gao; Song-He Yin; Yu-Mei Zhao (Journal of Molecular Histology, 2025)

Huangqi Guizhi Wuwu Decoction inhibits ferroptosis to improve cyclophosphamide induced immunosuppression through regulation of arachidonic acid metabolism - Li Wang; Fenyun Liu; Qianqian Wan; Yafei Xia; Qi Zhang; Jing Xun; Ping Li; Yuming Wang; Mei Li; Yuhong Bian; Huantian Cui (Journal of Molecular Histology, 2025)

DEHP and its metabolite MEHP exposure impairs endometrial decidualization during early pregnancy via up-regulation of Mtmr6 - Li-Ping Tan; Liu Yuan; Yan Zhang; Jun-Lin He; Xin Yin; Yi-Dan Ma; Xue-Mei Chen; Wei-Ke Li; Fang-Fang Li; Ru-Fei Gao (Reproductive Toxicology, 2025)

Multi-mineral dating of Archean granitoids of the Jiaobei Terrane: Decoding multiple tectono-thermal events in the eastern North China Craton - Yan-Ping Chen; Fan-Mei Kong; Xu-Ping Li; Hans-Peter Schertl (Precambrian Research, 2025)

Reductive transformation processes of ferrihydrite and U(VI) triggered by S2- under an anaerobic environment - Jiayu Song; Shirong Qiang; Huiyang Mei; Ping Li; Jianjun Liang; Qiaohui Fan (Journal of Hazardous Materials, 2025)

Links of abrupt climate events in the eastern Hexi Corridor to Atlantic meridional overturning circulation changes during the last glacial: Magnetoclimatological evidence of the Shagou loess record - Mei Sheng; Shiyu Yi; Xisheng Wang; Zongyao Li; Ping Sun; Yueyue Xin; Ke Hu; Zhenyu Yang (Global and Planetary Change, 2025)

Ratiometric photoelectrochemical aptasensor for ultrasensitive kanamycin detection based on superior photoactive high-entropy sulfide nanosheets coupling with dual-atom nanozyme inducing polarity switch - Jia-Lin Li; Li-Ping Mei; Ai-Jun Wang; Pei Song; Jiu-Ju Feng (Chemical Engineering Journal, 2025)

Polyethylene biodegradation by gut microbiota of Lasioderma serricorne: Isolation, identification, and mechanistic insights - Ming-Fei Wu; Pan-Pan Jia; Ling He; Li-Ping Ma; Yan Li; Lan-Chen Zhang; Dong-Mei Xie; Xiao-Bing Li; Tian-Nv Wang; De-Sheng Pei (Chemical Engineering Journal, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

A symbiotic bacterium regulates the detoxification metabolism of deltamethrin in Aedes albopictus - Si-jia Deng; Lei Tu; Lin Li; Ju-ping Hu; Ju-lin Li; Jian-xia Tang; Mei-chun Zhang; Guo-ding Zhu; Jun Cao (Pesticide Biochemistry and Physiology, 2025)

Production regularity of exosomes and the characteristics of miRNA in exosomes from Eriobotrya Japonica L. suspension cells - Hui-hua Li; Mei-fang Wu; Qiu-ping Ye; Fei Chen; Wei Wang; Jian-yu Shi (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Revealing the Oxidative Stress-Related Molecular Characteristics and Potential Therapeutic Targets of Schizophrenia through Integrated Gene Expression Data Analysis - Xiu-Mei Zhu; Ji Chen; Hua-Jie Ba; Chun Yang; Jian-Wei Liu; Rui Guo; Shi-Lin Li; Ping Huang; Cheng-Tao Li; Su-Hua Zhang (Molecular Neurobiology, 2025)

Genetic diversity assessment and disease resistance gene identification of Yunnan rice landraces - Mei Li; Rongping Li; Yunxiu Yang; Xiaoqiao Zhu; Huiling Zhang; Yun-Yue Wang; Ping He; Guangyu Han (European Journal of Plant Pathology, 2025)

Mechanistic insights into endometriosis: roles of Streptococcus agalactiae and L-carnitine in lesion development and angiogenesis - Yuan Zhuang; Ting Lyu; Yang Chen; Wei Li; Lei Tang; Shi-ping Xian; Peng-fei Yang; Lijie Wang; Qian-qian Zhang; Chaoming Mei; Yu-jing Lin; Zhixiang Yan; et al. (Angiogenesis, 2025)

Tanshinone IIA inhibits neuronal ferroptosis and relieves cerebral ischemia‒reperfusion injury by regulating miR-449a/ACSL4 - Huimin Yu; Yili Li; Yuehong Yang; Yanjin Qian; Xia Gao; Xichan Wang; Ping Zhan; Dekun Tang; Mei Qin; Yan Qian (Metabolic Brain Disease, 2025)

Lightweight deep learning model for embedded systems efficiently predicts oil and protein content in rapeseed - Mengshuai Guo; Huifang Ma; Xin Lv; Dan Wang; Li Fu; Ping He; Desheng Mei; Hong Chen; Fang Wei (Food Chemistry, 2025)

Discovery and configurations assignment of Ile/Leu-containing cyclic peptides with cytotoxic activity, Reniochpeptins A–D, from the marine sponge Reniochalina sp. - Shuai-Shuai Zhang; Zong-Mei Wu; Ying Wu; Ya-Jun Zeng; Yuan-Yuan Zhang; Xin-Li Lin; Si Zhang; Kai-Xuan Zhan; Hou-Wen Lin; Shu-Ping Wang (Phytochemistry, 2025)

Development of a shear strengthening conductive hydrogel for impact protection and distress signal emission - Juan Tan; Xi Li; Chuan Ru Zheng; Anna Tan; Xiu Chen Li; Hai Liang Ni; Wen Hao Yu; Yue Feng Bai; Ping Hu; Hong Mei Chen (Chemical Engineering Journal, 2025)

A Golden2-like transcription factor regulates Brassica napus seed vigor after artificial aging - Xiaoke Ping; Mei Yan; Jia Wang; Qianjun Ye; Taiyuan Zhang; Xiaojie Hu; Sheng Chen; Jiana Li; Liezhao Liu (Theoretical and Applied Genetics, 2025)

Raman spectroscopy coupled with chemometrics for identification of adulteration and fraud in muscle foods: a review - Haiyang Ma; Jiajun Guo; Guishan Liu; Delang Xie; Bingbing Zhang; Xiaojun Li; Qian Zhang; Qingqing Cao; Xiaoxue Li; Fang Ma; Yang Li; Guoling Wan; et al. (Critical Reviews in Food Science and Nutrition, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Cooperation of Lactoplantibacillus plantarum and polyethylene microplastics facilitated the disappearance of tetracycline during anaerobic fermentation of whole plant maize - Yubo Zhang; Pan Wang; Yu Tang; Chaosheng Liao; Xiaolong Tang; Pai Hou; Cheng Chen; Xiaokang Huang; Guangrou Lu; Lin Li; Mingjie Zhang; Fuxiang Li; et al. (Journal of Hazardous Materials, 2025)

A remotely triggered phase change hydrogel dressing for controlled release and promoting healing of infected wounds - Xiaolong Hu; Hongyan Zhang; Zuan-Tao Lin; Yu Chen; Hao Cheng; Bi-Huan Zhong; Yongli Li; Xiao-Ping Liao; Jian Sun; Mei X. Wu; Gang-Biao Jiang (Chemical Engineering Journal, 2025)

Designing multilayer interlocked architectures with vertical LDH nanosheets in ZIF-67 composite membranes for upgrading CO2 separation - Yan-Mei Zhang; Li-Hao Xu; Xiao-Xue Hu; Bing-Hong Chen; Xin-Ru Chen; Qian-Qian Li; Heng Mao; Zhi-Ping Zhao (Chemical Engineering Journal, 2025)

Structural integrity and near-infrared absorption of the LH1 complex of Thermochromatium tepidum: Influence from the C-terminal lysine residues of LH1 α-polypeptide - Yi-Hao Yan; Yu-Qian Li; Mei-Juan Zou; Long-Jiang Yu; Jian-Ping Zhang (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2025)

Preparation of highly functionalised biochar from hydrochloric acid activated bagasse for the efficient removal of metal ions - Mei Yang; Rimu Lu; Yichun Wei; Yingtao Guo; Lihong Lan; Jiajun Lu; Yexin Liao; Heping Li; Ping Lan; Zongliang Kou (Process Safety and Environmental Protection, 2025)

Untargeted qualitative and targeted quantitative analysis of saponins reveal differential chemotypes of Gynostemma pentaphyllum and G. longipes from different geographical origins - Hai-Zhen Liang; Mei-Yan Wang; Guang Yang; Gang Li; Jie Zhang; Lan Yao; Yi Nan; Chang-Liang Huang; Xiao-Juan Chen; Juan Song; Feng Cao; Bao-Lin Guo; et al. (Food Chemistry, 2025)

Estradiol Enhances Cerebellar Molecular Layer Interneuron-Purkinje Cell Synaptic Transmission and Improves Motor Learning Through ER-β in Vivo in Mice - Yong-Rui Piao; Mei-Rui Li; Ming-Ze Sun; Yang Liu; Chao-Yue Chen; Chun-Ping Chu; Yuki Todo; Zheng Tang; Chun-Yan Wang; Wen-Zhe Jin; De-Lai Qiu (The Cerebellum, 2025)

Characterizing Chinese saffron Origin, Age and grade using VNlR hyperspectral imaging and Machine learning - Jiahui Wu; Jing Nie; Hao Hu; Xinyue Xu; Chunlin Li; Hongkui Zhou; Peishi Feng; Hanyi Mei; Karyne M. Rogers; Ping Wang; Yuwei Yuan (Food Research International, 2025)

CXCL10 Enhances Acid-Sensing Ion Channel Currents in Rat Dorsal Root - Ting-Ting Liu; Chun-Yu Qiu; Xue-Mei Li; Wang-Ping Hu (Molecular Neurobiology, 2025)

Sequestration process and mechanism of U(VI) on montmorillonite-aspergillus niger composite - Rongyue Geng; Shirong Qiang; Huiyang Mei; Beihang Zhang; Ping Li; Jianjun Liang; Qiaohui Fan (Science of The Total Environment, 2025)

Z/E configuration controlled by a Taxus sesquiterpene synthase facilitating the biosynthesis of (3Z,6E)-α-farnesene - Xue Tang; Xian-Jing Zhang; Jing-Feng Pan; Kai Guo; Chun-Lin Tan; Qiao-Zhuo Zhang; Li-Ping Long; Rui-Feng Ding; Xue-Mei Niu; Yan Liu; Sheng-Hong Li (Phytochemistry, 2025)

Anti-inflammatory oxazole-, nitro- and hexahydropyrrolo[2,1-b]oxazole-containing abietane diterpenoid alkaloids from Salvia miltiorrhiza - Li-Xia Wang; Shao-Jie Shi; Li-Ping Long; Xiao-Ping He; Peng Zhang; Xiao-Wen Yang; Yan Liu; Xue-Mei Niu; Kai Guo; Sheng-Hong Li (Phytochemistry, 2025)

Comprehensive physicochemical indicators analysis and quality evaluation model construction for the post-harvest ripening rapeseeds - Qiuhui Xu; Jie Wang; Dan Wang; Xin Lv; Li Fu; Ping He; Desheng Mei; Hong Chen; Fang Wei (Food Chemistry, 2025)

The complex interplay of flooding intensity and land use on soil microbial communities in riparian zones: Insights for ecological restoration - Kai Zhu; Fei Ye; Yu Mei; Weitao Jia; Xiai Zhu; Shuzhen Li; Shengjun Wu; Songlin Zhang; Ping Huang (CATENA, 2025)

Varied chromosome distribution behaviours during meiosis in triploid Chinese chives contribute to the formation of viable pollen - Peng-Qiang Yao; Li-Hua Xie; Mei-Yu Li; Si-Qian Jiao; Shuai-Zheng Qi; Zhe Wang; Shi-Ping Cheng (Chromosome Research, 2024)

Promotion of antibiotic-resistant genes dissemination by the micro/nanoplastics in the gut of snail Achatina fulica - Yan-Mei Da; Xiao-Ru Yang; Ming-Jun Li; Shun-Shun Li; Ze-Ping Gao; Ying Zhang; Jian-Qiang Su; Guo-Wei Zhou (Science of The Total Environment, 2024)

Miocene evolution of vegetation, climate, and elevation in the Wulan Basin of northeast Tibetan Plateau based on a CRACLE analysis of palynological assemblages - Xiao-Mei Li; Jia-Yi Chen; Zhen-Dong Cao; Li-Ming Liu; Si-Hang Zhang; Yun-Zhe Zhang; Li-Jie Wei; San-Ping Xie (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Tectonic-climate-wildfire coupling during the Miocene in the northeastern Qinghai-Tibetan Plateau - Li-Ming Liu; Zhen-Dong Cao; Xiao-Mei Li; Si-Hang Zhang; Yun-Zhe Zhang; Jia-Yi Chen; De-Fei Yan; San-Ping Xie (Journal of Asian Earth Sciences, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Study of Cerchar abrasive parameters of monomineralic rocks and its application for evaluating cutting efficiency - Xin-Fang Li; Xiao-Ping Zhang; Shao-Hui Tang; Wei-Qiang Xie; Xin-Mei Yang; Quan-Sheng Liu (International Journal of Rock Mechanics and Mining Sciences, 2024)

NUS1 Variants Cause Lennox-Gastaut Syndrome Related to Unfolded Protein Reaction Activation - Nan-Xiang Shen; Xiao-Chong Qu; Jing Yu; Cui-Xia Fan; Fu-Li Min; Ling-Ying Li; Ming-Rui Zhang; Bing-Mei Li; Jie Wang; Na He; Wei-Ping Liao; Yi-Wu Shi; et al. (Molecular Neurobiology, 2024)

Short-term usage of proton pump inhibitors during admission was associated with increased risk of rehospitalization in critically ill patients with myocardial infarction: a cohort study - Jia-De Zhu; Li-Juan Yang; Jian-Nan Zhao; Ping Wang; Yi-Hua Li; Xue-Sha Zhang; Jian-Mei Pan; Meng-Han Jiang; Hai-Ying Yang; Sun-Jun Yin; Gong-Hao He (European Journal of Clinical Pharmacology, 2024)

Molecular Cloning and Functional Analysis of ScHAK10 Gene Promoter from Sugarcane (Saccharum officinarum L.) - Hai-Bin Luo; Cheng-Mei Huang; Hui-Qing Cao; Yuan-Wen Wei; Lin Xu; Kai-Chao Wu; Zhi-Nian Deng; Xing-Jian Wu; Li-Ping Ye; Xiao-Ping Yi (Tropical Plant Biology, 2024)

Predicting the potential deterioration of Barrett’s esophagus based on gut microbiota: a Mendelian randomization analysis - Conghan Li; Panyin Shu; Taiyu Shi; Yuerong Chen; Ping Mei; Yizhong Zhang; Yan Wang; Xinyan Du; Jianning Wang; Yixin Zhang; Bin Liu; Zhijin Sheng; et al. (Mammalian Genome, 2024)

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

Antibacterial and gut health effects of Amomum tsao‐ko in aquatic feed: A sustainable alternative to chemical antibiotics - Weiyao Peng; Guohui Liao; Lianzhang Wu; Jian Zhang; Juncai He; Penghui Gao; Yunsheng Cha; Shengjun You; Mei Huang; Jilan Zhou; Yuqiu He; Yi Yang; et al. (Journal of Fish Biology, 2024)
Amomum tsao‐ko Crevost et Lemarie (Zingiberaceae), an aromatic plant, has been considered to have diverse medicinal values and economic significance. It has been reported to possess antibacterial, antioxidant, and antidiabetic effects. With the increasing risk of diseases in aquaculture, there is a need for alternative solutions to chemical antibiotics. Plant extracts have shown promise as natural feed additives for aquatic animals. In this study, the antibacterial effect of Amomum tsao‐ko crude extracts was evaluated using the Oxford cup method. The extracts exhibited significant antimicrobial activity against Salmonella typhimurium and Salmonella enteritidis . Furthermore, the addition of Amomum tsao‐ko to fish feed resulted in notable changes in the gut structure of zebrafish and tilapia. The length and morphology of intestinal villi were enhanced, promoting improved digestion. Analysis of the gut microbial community revealed that Amomum tsao‐ko supplementation induced key changes in the gut microbial community composition of both zebrafish and tilapia. Notably, a 1% inclusion of Amomum tsao‐ko resulted in a marked rise in Proteobacteria levels in zebrafish, which diminished at 10% dosage. The supplement elicited mixed reactions among other bacterial phyla like Actinobacteria and Verrucomicrobiota. Fluctuations were also observed at the genus level, pointing to the concentration of Amomum tsao‐ko playing a pivotal role in influencing the structure of intestinal bacteria. The findings of this study suggest that Amomum tsao‐ko has antibacterial properties and can positively influence the gut health of fish. The potential use of Amomum tsao‐ko as a natural feed additive holds promise for improving aquaculture practices and reducing reliance on chemical antibiotics. Further research is needed to explore the full potential and applications of Amomum tsao‐ko in fish feed development.

T Cells Trafficking into the Brain in Aging and Alzheimer’s Disease - Yue-Zhang Ma; Jia-Xin Cao; Yi-Shu Zhang; Xiao-Mei Su; Yu-Hong Jing; Li-Ping Gao (Journal of Neuroimmune Pharmacology, 2024)

The fabrication of Mn single atoms/clusters on Al2O3 for enhanced catalytic NO oxidation - Xiao-Ke Hou; Hui-Xin Zhang; Yi-Bo Wang; Jin-Ping Zhang; Xin Gao; Lei Chen; Chao Li; Hong-Mei Jing; Chi He; Qiang Lu; Chun-Ran Chang (Fuel, 2024)

Attribution analysis of groundwater level fluctuation in the Xinxiang section of the Lower Yellow River’s suspended river after the construction of the Xiaolangdi Reservoir - He Li; Jianhua Ping; Wei Leng; Xuemei Mei; Min Zhang; Jiaqi Liu (Journal of Geographical Sciences, 2024)

Human health risk assessment and toxic effect of heavy metal(loid)s in Bamboo shoot products - Yu-Mei Xie; Meng-Yan Zhang; Fei-Peng Liu; Cheng-Chen Wang; Wen-Yuan Dong; Chun-Mei Xu; Xin Li; Wu-Mei Xu; Ping Xiang (Journal of Environmental Chemical Engineering, 2024)

Environmentally relevant concentrations of benzophenones exposure disrupt intestinal homeostasis, impair the intestinal barrier, and induce inflammation in mice - Yu-Jia Lin; Hong-Mei Li; Yan-Rong Gao; Ping-Fan Wu; Bin Cheng; Chen-Long Yu; Yu-Xin Sheng; Hai-Ming Xu (Environmental Pollution, 2024)

Synergistic signal amplification of ultrathin nanowire-like PtCoFeRuMo high-entropy nanozyme and Z-scheme WO3/ZnIn2S4 heterostructure for split-typed photoelectrochemical aptasensing of myoglobin - Fan Xu; Ben-Fang Xu; Qing-Ying Ai; Ai-Jun Wang; Li-Ping Mei; Pei Song; Jiu-Ju Feng (Chemical Engineering Journal, 2024)

Hybrid origin and hybrid status of the endangered Ilex sanqingshanensis revealed by molecular and morphological evidence - Wei-li Liu; Dan-qi Li; Yi-ping Zou; Ming-zhuo Hao; Zhi-yong Zhang; Deng-mei Fan; Yi Yang (Plant Systematics and Evolution, 2024)

Decoding the genome of bloodsucking midge Forcipomyia taiwana (Diptera: Ceratopogonidae): Insights into odorant receptor expansion - Ming-Der Lin; Chia-Hsien Chuang; Chih-Hsin Kao; Shu-Hwa Chen; Szu-Chieh Wang; Ping-Heng Hsieh; Guan-Yu Chen; Chun-Chia Mao; Jeng-Yi Li; Mei-Yeh Jade Lu; Chung-Yen Lin (Insect Biochemistry and Molecular Biology, 2024)

A bipolar SMPS network for measuring atmospheric aerosols using natural air ions - Yiran Li; Jin Wu; Hao Wu; Xiaomeng Liu; Qi Zhou; Yiqun Lu; Yuhang Wu; Mengyu Liu; Hengjia Ou; Shixin Mai; Xuehui He; Huaying Song; et al. (Atmospheric Environment, 2024)

Geochemistry and P-T-t evolution of Paleoproterozoic metapelites of the Zhengjiapo BIF-type iron mine, Jiaobei terrane, North China Craton - Yan-Rong Chen; Xu-Ping Li; Zeng-Sheng Li; Da-Peng Li; Fan-Mei Kong; Hans-Peter Schertl; Yan-Jing Chen (Precambrian Research, 2024)

Erratum to ‘Co(CO3)0.5OH•0·11H2O as superior peroxymonosulfate activator for ciprofloxacin degradation via co-acting mechanism of low & high-valent cobalt and oxygen vacancy’ [J. Environ. Chem. Eng. 12 (2024) 111872] - Jiaojiao Yang; Minghao Xu; Mei Qin; Ping Li; Hui Liu (Journal of Environmental Chemical Engineering, 2024)

Molecular mechanism of efficient degradation of TPM dyes by Serratia species WKD at high temperature - Yi Wei; Xin-Jiao Dong; Gang Li; Huan Wu; Lin-Na Du; Jia-Cheng Zhou; Jun Zhang; Yan-Ping Xiao; Yue-Mei Shang; Hong-Xia Liu (International Biodeterioration & Biodegradation, 2024)

Host-guest synergistic hydrogen bond triggered signal amplification for visualizing the plant hormone salicylic acid - A-Ling Tang; Li-Long Zhang; Shuai Tan; Ping Yang; Wei Niu; Mei-Hong Ge; Lin-Lin Yang; Pei-Yi Wang; Li-Wei Liu; Xiang Zhou; Song Yang (Chemical Engineering Journal, 2024)

Remote effects of Tibetan Plateau spring land temperature on global subseasonal to seasonal precipitation prediction and comparison with effects of sea surface temperature: the GEWEX/LS4P Phase I experiment - Yongkang Xue; Ismaila Diallo; Aaron A. Boone; Yang Zhang; Xubin Zeng; William K. M. Lau; J. David Neelin; Tandong Yao; Qi Tang; Tomonori Sato; Myung-Seo Koo; Frederic Vitart; et al. (Climate Dynamics, 2024)
The prediction skill for precipitation anomalies in late spring and summer months—a significant component of extreme climate events—has remained stubbornly low for years. This paper presents a new idea that utilizes information on boreal spring land surface temperature/subsurface temperature (LST/SUBT) anomalies over the Tibetan Plateau (TP) to improve prediction of subsequent summer droughts/floods over several regions over the world, East Asia and North America in particular. The work was performed in the framework of the GEWEX/LS4P Phase I (LS4P-I) experiment, which focused on whether the TP LST/SUBT provides an additional source for subseasonal-to-seasonal (S2S) predictability. The summer 2003, when there were severe drought/flood over the southern/northern part of the Yangtze River basin, respectively, has been selected as the focus case. With the newly developed LST/SUBT initialization method, the observed surface temperature anomaly over the TP has been partially produced by the LS4P-I model ensemble mean, and 8 hotspot regions in the world were identified where June precipitation is significantly associated with anomalies of May TP land temperature. Consideration of the TP LST/SUBT effect has produced about 25–50% of observed precipitation anomalies in most hotspot regions. The multiple models have shown more consistency in the hotspot regions along the Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train. The mechanisms for the LST/SUBT effect on the 2003 drought over the southern part of the Yangtze River Basin are discussed. For comparison, the global SST effect has also been tested and 6 regions with significant SST effects were identified in the 2003 case, explaining about 25–50% of precipitation anomalies over most of these regions. This study suggests that the TP LST/SUBT effect is a first-order source of S2S precipitation predictability, and hence it is comparable to that of the SST effect. With the completion of the LS4P-I, the LS4P-II has been launched and the LS4P-II protocol is briefly presented.

Metabolomics analysis to interpret changes in physiological and metabolic responses to chronic heat stress in Pekin ducks - Xiangyi-Yi Zeng; Arshad Javid; Gang Tian; Ke-Ying Zhang; Shi-Ping Bai; Xue-Mei Ding; Jian-Ping Wang; Li Lv; Yue Xuan; Shan-Shan Li; Qiu-Feng Zeng (Science of The Total Environment, 2024)

Co(CO3)0.5(OH)•0.11H2O as superior peroxymonosulfate activator for ciprofloxacin degradation via co-acting mechanism of low & high-valent cobalt and oxygen vacancy - Jiaojiao Yang; Minghao Xu; Mei Qin; Ping Li; Hui Liu (Journal of Environmental Chemical Engineering, 2024)

Constructing mesoporous biochar derived from waste carton: Improving multi-site adsorption of dye wastewater and investigating mechanism - Yan-Shan Wang; Tong-Rong Huo; Yan Wang; Jia-Wen Bai; Ping-Ping Huang; Chen Li; Shi-Yu Deng; Hong Mei; Jun Qian; Xiao-Chi Zhang; Chen Ding; Qiu-Yu Zhang; et al. (Environmental Research, 2024)

Mechanism of Antidepressant Action of (2R,6R)-6-Hydroxynorketamine (HNK) and Its Compounds: Insights from Proteomic Analysis - Chaohui Zhen; Chong Wang; Yanjun Ma; Yuli Pang; Feiyue Cai; Jiali Meng; Yuefei He; Ping Xiao; Jianxi Liu; Xi Mei; Shupeng Li; Guanzheng Wu; et al. (Molecular Neurobiology, 2024)

The clinical trajectory of peripheral blood immune cell subsets, T-cell activation, and cytokines in septic patients - Xuan Lu; Cong-Ying Song; Ping Wang; Li Li; Li-Ying Lin; Shuai Jiang; Jia-Ning Zhou; Meng-Xiao Feng; Yun-Mei Yang; Yuan-Qiang Lu (Inflammation Research, 2024)

Relationship of individual and mixed urinary metals exposure with liver function in the China National Human Biomonitoring (CNHBM) of Zhejiang Province - Ping Cheng; Yi Tao; Jinfeng Hu; Hongxin Wang; Ruifang Zhao; Shenghua Mei; Yin Yang; Fugen Ye; Zhijian Chen; Hao Ding; Mingluan Xing; Peiwei Xu; et al. (Chemosphere, 2023)

Novel GdTaO4 phase for efficient photocatalytic degradation of organic dye under visible light irradiation: An X-ray spectroscopic investigation - Alageshwaramoorthy Krishnaprasanth; Pandian Mannu; Seetha Mahalingam; Dhanaprabhu Pattappan; Asokan Kandasami; Yi-Ting Lai; Yoshitake Masuda; Han-Wei Chang; Mei-Yu Chen; Ping-Hung Yeh; Chung-Li Dong (Chemosphere, 2023)

Plastisphere characterization in habitat of the highly endangered Shinisaurus crocodilurus: Bacterial composition, assembly, function and the comparison with surrounding environment - Mujiao Xie; Mei Lv; Zhiwen Zhao; Linmiao Li; Haiying Jiang; Yepin Yu; Xiujuan Zhang; Ping Liu; Jinping Chen (Science of The Total Environment, 2023)

Extraction and characterization of anti-virus anthraquinones from Nicotiana tabacum-derived Aspergillus oryzae YNCA1220 - Feng-Xian Yang; Yue-Yu Ma; Yu-Ping Wu; Gao-Kun Zhao; Yong-Ping Li; Zhen-Jie Li; Xue-Mei Li; Yin-Ke Li; Wei-Guang Wang; Min Zhou; Guang-Hui Kong; Qiu-Fen Hu (Pesticide Biochemistry and Physiology, 2023)

Bi0·5Na0·5TiO3/ZnO Z-scheme heterojunction for piezo-photocatalytic water remediation: Mechanical energy harvesting and energy band configuration - Peng Wang; Wanqian Cai; Fangyuan Yu; Ping Zhou; Mei Lin; Cong Lin; Tengfei Lin; Min Gao; Chunlin Zhao; Xiangqi Li; Xiao Wu (Chemosphere, 2023)

Experimental research progress of grid to rod fretting in pressurized water reactors - Yong-jun Jiao; Zheng-yang Li; Zeng-ping Pu; Mei-yin Zheng; Quan-yao Ren; Zhen-bing Cai; Yin-wei Wu; Sui-zheng Qiu (Annals of Nuclear Energy, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

A novel bacteriocin RSQ01 with antibacterial activity and its application and metabolomic mechanism in milk preservation - Yan-Mei Zhang; Lin-Yu Yang; Jian-Ping Ying; Chao-Min Fu; Gang Wu; Xiao-Ran Li; Qi-Lin Zhang (Food Control, 2023)

Self-checking dual-modal aptasensor based on hybrid Z-scheme heterostructure of Zn-defective CdS/ZnS for oxytetracycline detection - Pei Song; Ping Qu; Min Wang; Ai-Jun Wang; Yadong Xue; Li-Ping Mei; Jiu-Ju Feng (Analytica Chimica Acta, 2023)

Antimony(III) removal by biogenic manganese oxides formed by Pseudomonas aeruginosa PA-1: kinetics and mechanisms - Qing Li; Yun He; Aijiang Yang; Xia Hu; Fang Liu; Jincheng Mu; Shixue Mei; Lin-Ping Yang (Environmental Science and Pollution Research, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Bisabolane-type sesquiterpenoids with potential anti-inflammatory and anti-HIV activities from the stems and leaves of Morinda citrifolia - Ying-Ying Zhao; Yu-Jie Li; Xiao-Mei Yu; Qin-Ting Su; Li-Wen Wang; Yu-Shu Zhu; Yan-Hui Fu; Guang-Ying Chen; Yan-Ping Liu (Natural Product Research, 2023)

Ancestors of Ulmus parvifolia from late Miocene sediments in Yunnan, Southwest China and its future distribution - Ping Lu; Jian-Wei Zhang; Xiao-Qing Liang; Hong-Mei Li; De-Liang Li (Review of Palaeobotany and Palynology, 2023)

Three new isoquinoline alkaloids from the cigar tobacco-derived endophytic fungus Aspergillus felis - Yue-Yu Ma; Gui Pu; Xue-Ju Cha; Rui-Feng Xiong; Guang-Hai Zhang; Heng Yao; Mei-Fen Bao; Guang-Hui Kong; Yin-Ke Li; Qiu-Fen Hu; Yu-Ping Wu (Phytochemistry Letters, 2023)

Genome-wide Transcriptome Analysis Reveals the Gene Regulatory Network in Star Fruit Flower Blooming - Si Qin; Xiao-Ping Li; Chun-Mei Wu; Le You; Donghui Peng; Sagheer Ahmad; Hui Ren; Zhong-Jian Liu; Jun-Wen Zhai; Sha-Sha Wu (Tropical Plant Biology, 2023)

Effects of disinfectants, sponge densities, water circulation rates, and vibration frequency on the artificial incubation of redclaw crayfish embryos - Cheng Shun; Jiang Wen-ping; Liu Shi-li; Chi Mei-li; Zheng Jian-bo; Liu Yi-nuo; Hang Xiao-ying; Peng Miao; Li Fei; Wang Dan-li (Aquaculture, 2023)

Low-dose ionizing radiation: Effects on the proliferation and migration of lens epithelial cells via activation of the Wnt/β-catenin pathway - Ping Wang; Yu-Wen Li; Xue Lu; Ya Liu; Xue-Lei Tian; Ling Gao; Qing-Jie Liu; Li Fan; Mei Tian (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2023)

Melatonin inhibits senescence-associated melanin pigmentation through the p53-TYR pathway in human primary melanocytes and the skin of C57BL/6 J mice after UVB irradiation - Li-Ping Ma; Meng-Meng Liu; Fang Liu; Bo Sun; Si-Nian Wang; Jie Chen; Hui-Jie Yu; Juan Yan; Mei Tian; Ling Gao; Qing-Jie Liu (Journal of Molecular Medicine, 2023)
UVB exposure accelerates skin aging and pigmentation. Melatonin effectively regulates tyrosinase (TYR) activity and aging. The purpose of this study was to determine the association between premature senescence and pigmentation, and the mechanism of melanin synthesis effected by melatonin. Primary melanocytes were extracted and identified from the male foreskin. To inhibit TYR expression, primary melanocytes were transduced with the lentivirus pLKD-CMV-EGFP-2A-Puro-U6-TYR. The wild-type TYR ( + / + ) and TYR (–/–) or TYR ( + /–) knockout C57BL/6 J mice were used to determine the role of TYR on melanin synthesis in vivo. Results showed that UVB-induced melanin synthesis is dependent on TYR in primary melanocytes and mice. Furthermore, in primary melanocytes pretreated with Nutlin-3 or PFT-α to up or downregulate p53, results showed that premature senescence and melanin synthesis increased in primary melanocytes after UVB irradiation at 80 mJ/cm 2 , and further increased after being treated with Nutlin-3, while significantly decreased with PFT-α. In addition, melatonin inhibited UVB-induced premature senescence associated with inactivation of p53 and phosphorylation of p53 on Ser15 (ser-15), a decrease of melanin synthesis accompanied by reduced TYR expression. Moreover, skin erythema and pigmentation induced by UVB were reduced in the dorsal and ear skin of mice topically pretreated with 2.5% melatonin. These indicate that melatonin inhibits UVB-induced senescence-associated pigmentation via the p53-TYR pathway in primary melanocytes and prevents pigmentation obviously in the dorsal and ear skin of C57BL/6 J mice after UVB irradiation. Key messages P53 links UVB irradiation-induced senescence and senescence-associated pigmentation and regulates TYR in primary melanocytes after UVB irradiation. Melatonin inhibits senescence-associated pigmentation through the p53-TYR pathway in primary melanocytes. Melatonin prevents skin erythema and melanin pigmentation induced by UVB irradiation in the dorsal and ear skin of C57BL/6J mice.

Experimental Study of Similar Simulated Material Proportioning for Small Scale Models - Yongjian Zhu; Peng Li; Ping Wang; Heng Ren; Chengcheng Mei; Mingxing Wei (Geotechnical and Geological Engineering, 2023)

The effect of episodic foresight on intertemporal decision-making: the role of future self-continuity and perceived control - Hong-Yue Sun; Yuan-Ping Jiang; Xin Wang; Li-Ying Cui; Hong-Mei Sun (Cognitive Processing, 2023)

Comparison of two commercial methods with a UHPLC–MS/MS method for the determination of multiple mycotoxins in cereals - Ying-yue Zhang; Mei-juan Zhao; Chun-yao Liu; Kai Ma; Tian-yu Liu; Fei Chen; Li-na Wu; De-jun Hu; Guang-ping Lv (Food Chemistry, 2023)

In Vitro Antifungal Activity of Azoles and Other Antifungal Agents Against Pathogenic Yeasts from Vulvovaginal Candidiasis in China - Siyue Kan; Nana Song; Qiuyu Pang; Huan Mei; Hailin Zheng; Dongmei Li; Fan Cui; Guixia Lv; Ruifang An; Ping Li; Zhengai Xiong; Shangrong Fan; et al. (Mycopathologia, 2023)

Isothermal exponential amplification reactions triggered by circular templates (cEXPAR) targeting miRNA - Xue-mei Qu; Xiao-dong Ren; Ning Su; Xian-ge Sun; Shao-li Deng; Wei-ping Lu; Qing Huang (Molecular Biology Reports, 2023)

Tailoring enzymatic loading capacity on CdS nanorods@ZnIn2S4 nanosheets 1D/2D heterojunctions: Toward ultrasensitive photoelectrochemical bioassay of tobramycin - Rui Hu; Ben-Fang Xu; Yadong Xue; Zhi-Zhi Xu; Ai-Jun Wang; Li-Ping Mei; Pei Song; Jiu-Ju Feng (Chemosphere, 2023)

Quality assessment of variable collagen tissues of sea cucumber (Stichopus japonicus) body wall under different heat treatment durations by label-Free proteomics analysis - Yi-Zhen Huang; Yi-Sha Xie; Yan-Xin Li; Mei-Yu Zhao; Na Sun; Hang Qi; Xiu-Ping Dong (Food Research International, 2023)

Distribution and physical–biological controls of dimethylsulfide in the western tropical Indian Ocean during winter monsoon - Shi-Mei Liang; Xing Zhai; Cheng-Xuan Li; Ming Xin; Ping Sun; Xuan-Li Liu; Lin Liu; Bao-Dong Wang (Frontiers in Marine Science, 2023)
New field observation on distribution, turnover, and sea–air flux of three dimethylated sulfur compounds (dimethylsulfide (DMS), dimethylsulfoniopropionate, and dimethylsulfoxide) in the western tropical Indian Ocean (WTIO; 4°N–10°S, 61°–65°E) were conducted under the major Global Change and Air–Sea Interaction Program during the 2021/2022 Northeast Monsoon (December 21, 2021 to January 11, 2022). Significantly high surface concentrations of DMS were identified in the region of the Seychelles–Chagos Thermocline Ridge (SCTR; 5°–10°S). This occurred because the shallow thermocline/nitracline and associated upwelling fueled biological production of DMS in the subsurface, which was brought to the surface through vertical mixing. The calculated sea–air DMS flux was also significantly strong in the SCTR region during the Northeast Monsoon owing to combination of high wind speed and high surface concentration of DMS. This finding is similar to results obtained previously during the Southwest Monsoon, suggesting that the SCTR region is an area of active DMS emission during both the Northeast Monsoon and the Southwest Monsoon. Microbial consumption was the dominant pathway of DMS removal, accounting for 74.4% of the total, whereas the processes of photolysis (17.7%) and ventilation (7.9%) were less important. Future work should be undertaken in the WTIO to establish how DMS emission is linked to aerosol properties and climate change.

Heavy metal(loid)s in agricultural soil from main grain production regions of China: Bioaccessibility and health risks to humans - Cheng-Chen Wang; Qiao-Chu Zhang; Shao-Guo Kang; Meng-Ying Li; Meng-Yan Zhang; Wu-Mei Xu; Ping Xiang; Lena Q. Ma (Science of The Total Environment, 2023)

Two new tetrahydroisoquinoline alkaloids from Portulaca oleracea - Kai-Jun Tang; Yu Chen; Jing Li; Xu Tao; Lu-Ping Yang; Tian-Yun Jin; Jia-Shun Zhu; Yu Zhao; Tao Shen; Xiao-Ning Wang; Dong-Mei Ren; Lan Xiang (Phytochemistry Letters, 2023)

Effects of light color, photoperiod, and growth-related gene interference or overexpression on the survival, growth, or physiological and biochemical indices of red claw crayfish juveniles - Shun Cheng; Jian-bo Zheng; Yong-yi Jia; Mei-li Chi; Wen-ping Jiang; Shi-li Liu; Fei Li; Yi-nuo Liu; Zhi-min Gu; Dan-li Wang (Aquaculture, 2023)

Ultrasonic-assisted stewing enhances the aroma intensity of chicken broth: A perspective of the aroma-binding behavior of fat - Jun Qi; Chuan-kang Jia; Wen-wen Zhang; Hui-min Yan; Qing-yuan Cai; Xiu-ning Yao; Kuo Xu; Ying Xu; Wen-ping Xu; Guo-yuan Xiong; Mei-qi Li (Food Chemistry, 2023)

From lab to practical: An ammonia-powered fuel cell electric golf cart system - Lingling Zhai; Chiu Shek Wong; Honglei Zhang; Pei Xiong; Xiangdang Xue; Yiu Lun Ho; Cuidong Xu; Yat Chi Fong; Jie Mei; Wing Wa Chan; Shu Chuen Ip; Shuangxia Niu; et al. (Chemical Engineering Journal, 2023)

A Fundamental Role of Slope Aspect and Elevation in Controlling Diversity Patterns of Soil Bacterial Communities: Insights from an Arid-Montane Ecosystem in China - Long-Fei Chen; Jun-Qia Kong; Zhi-Bin He; Wen-Zhi Zhao; Ming-Dan Song; Yue-Mei Li; Yuan Gao; Shu-Ping Yang (Journal of Soil Science and Plant Nutrition, 2022)

Copper Toxicity Differentially Regulates the Seedling Growth, Copper Distribution, and Photosynthetic Performance of Citrus sinensis and Citrus grandis - Xin-yu Li; Mei-lan Lin; Ping-ping Hu; Ning-wei Lai; Zeng-rong Huang; Li-song Chen (Journal of Plant Growth Regulation, 2022)

A1 Adenosine Receptor Activation Inhibits P2X3 Receptor–Mediated ATP Currents in Rat Dorsal Root Ganglion Neurons - Jia-Wei Hao; Wen-Long Qiao; Qing Li; Shuang Wei; Xue-Mei Li; Ting-Ting Liu; Chun-Yu Qiu; Wang-Ping Hu (Molecular Neurobiology, 2022)

Paenibacillus hamazuiensis sp. nov., a bacterium isolated from Hamazui hot spring in Yunnan province, south-west China - Juan Wang; Ming Deng; En-Min Zhou; Lei Ran; Cui-Ping Miao; Yi-Qing Li; Jun-Mei Ding; Shu-Kun Tang (Archives of Microbiology, 2022)

Integrated genetic mapping and transcriptome analysis reveal the BnaA03.IAA7 protein regulates plant architecture and gibberellin signaling in Brassica napus L. - Xiaoke Ping; Qianjun Ye; Mei Yan; Jianyan Zeng; Xingying Yan; Haitao Li; Jiana Li; Liezhao Liu (Theoretical and Applied Genetics, 2022)

Effect of posaconazole on the concentration of intravenous and oral cyclosporine in patients undergoing hematopoietic stem cell transplantation - Li-E Zhu; Hui-Ping Huang; Yi-Peng Cai; Yan Wang; Bao-Hua Xu; Mao-Bai Liu; Xue-Mei Wu (European Journal of Clinical Pharmacology, 2022)

Differential expression and functional analysis of circRNA in the ovaries of Yili geese at different egg-laying stages - Xiao-yu Zhao; Ying-ping Wu; Hai-ying Li; Yan Cao; Zhi-yong Mei; Jia-hui Li (Genes & Genomics, 2022)

Functional analysis of HADH c.99C>G shows that the variant causes the proliferation of pancreatic islets and leu-sensitive hyperinsulinaemia - Wu Long; Yue-Bing Wang; Peng-Fei Qu; Lin Ma; Si-Jie Wei; Yan-Mei Xi; Jin-Liang Du; Xue Tang; Kai Liu; Yu-Hua Li; Pu-Ping Lei (Journal of Genetics, 2022)

Association of cognitive impairment and reduced cortical thickness in prefrontal cortex and anterior cingulate cortex with treatment-resistant depression - Mu-Hong Chen; Wan-Chen Chang; Pei-Chi Tu; Wei-Chen Lin; Cheng-Ta Li; Wen-Sheng Huang; Ya-Mei Bai; Shih-Jen Tsai; Tung-Ping Su (Brain Imaging and Behavior, 2022)

CaMKIIα Signaling Is Required for the Neuroprotective Effects of Dl-3-n-Butylphthalide in Alzheimer’s Disease - Bing-qiu Li; Ling-zhi Xu; Fang-yu Li; Ying Li; Yu Zhao; Heng Zhang; Mei-na Quan; Jian-ping Jia (Molecular Neurobiology, 2022)

Astragalus Polysaccharides Reduce High-glucose-induced Rat Aortic Endothelial Cell Senescence and Inflammasome Activation by Modulating the Mitochondrial Na+/Ca2+ Exchanger - Xin-Yu Miao; Xiao-Xiao Zhu; Zhao-Yan Gu; Bo Fu; Shao-Yuan Cui; Yuan Zu; Ling-Jun Rong; Fan Hu; Xiang-Mei Chen; Yan-Ping Gong; Chun-Lin Li (Cell Biochemistry and Biophysics, 2022)

Prenylated coumarins from the fruits of Artocarpus heterophyllus with their potential anti-inflammatory and anti-HIV activities - Lei Tao; Ya-Ting Zhuo; Ze-Hua Qiao; Juan Li; Hao-Xuan Tang; Qiao-Mei Yu; Yun-Yao Liu; Yan-Ping Liu (Natural Product Research, 2022)

Biological monitoring and health assessment of 21 metal(loid)s in children and adolescents in Liuzhou City, Southwest China - Yaping Li; Yu Zhang; Meng Yu; Liqin Hu; Ting Zeng; Ling Liu; Limei Wang; Liangqiong Deng; Xiang Li; Ping Liu; Dingyuan Zeng; Surong Mei (Environmental Science and Pollution Research, 2022)

Size distributions and dry deposition fluxes of water-soluble inorganic nitrogen in atmospheric aerosols in Xiamen Bay, China - Shui-Ping Wu; Xiang Li; Yang Gao; Mei-Jun Cai; Chao Xu; James J. Schwab; Chung-Shin Yuan (Journal of Atmospheric Chemistry, 2022)

Cancer metabolism and tumor microenvironment: fostering each other? - Yiyuan Yuan; Huimin Li; Wang Pu; Leilei Chen; Dong Guo; Hongfei Jiang; Bo He; Siyuan Qin; Kui Wang; Na Li; Jingwei Feng; Jing Wen; et al. (Science China Life Sciences, 2022)

Biogeography of culturable marine bacteria from both poles reveals that ‘everything is not everywhere’ at the genomic level - Qi‐Long Qin; Zhi‐Bin Wang; Qian‐Qian Cha; Sha‐Sha Liu; Xue‐Bing Ren; Hui‐Hui Fu; Mei‐Ling Sun; Dian‐Li Zhao; Andrew McMinn; Yin Chen; Xiu‐Lan Chen; Yu‐Zhong Zhang; et al. (Environmental Microbiology, 2022)
Summary Based on 16S rRNA gene analyses, the same bacterial operational taxonomic units (OTUs) are common to both the Arctic and Antarctic oceans, supporting the concept ‘everything is everywhere’. However, whether the same OTUs from both poles have identical genomes, i.e. whether ‘everything is still everywhere’ at the genomic level has not yet been examined systematically. Here, we isolated, sequenced and compared the genomes of 45 culturable marine bacteria belonging to three genera of Salinibacterium , Psychrobacter and Pseudoalteromonas from both polar oceans. The bacterial strains with identical 16S rRNA genes were common to both poles in every genus, and four identical genomes were detected in the genus Salinibacterium from the Arctic region. However, no identical genomes were observed from opposite poles in this study. Our data, therefore, suggest that ‘everything is not everywhere’ at the genomic level. The divergence time between bacteria is hypothesized to exert a strong impact on the bacterial biogeography at the genomic level. The geographical isolation between poles was observed for recently diverged, highly similar genomes, but not for moderately similar genomes. This study thus improves our understanding of the factors affecting the genomic‐level biogeography of marine microorganisms isolated from distant locations.

Association between ambient air pollution and multiple sclerosis: a systemic review and meta-analysis - Chao Tang; Qing-Ru Li; Yan-Mei Mao; Yuan-Rui Xia; Heng-Sheng Guo; Jun-Ping Wang; Zong-Wen Shuai; Dong-Qing Ye (Environmental Science and Pollution Research, 2021)

Serum levels of polychlorinated biphenyls and stroke risk among Chinese: a hospital-based case–control study - Ping Li; Ying Dan; Shuangying Li; Qiaolian Zhang; Ya Su; Mei Lu (Acta Neurologica Belgica, 2021)

Methane Concentration in the Heartwood of Living Trees and Estimated Methane Emission on Stems in Upland Forests - Zhi-Ping Wang; Huan-Long Li; Hong-Hui Wu; Shi-Jie Han; Jian-Hui Huang; Xi-Mei Zhang; Xing-Guo Han (Ecosystems, 2021)

Triterpene saponins from tea seed pomace ( Camellia oleifera Abel) and their cytotoxic activity on MCF-7 cells in vitro - Xin-Fu Zhang; Ying-Ying Han; Tai-Mei Di; Li-Ping Gao; Tao Xia (Natural Product Research, 2021)

Size distributions and health risks of particle-bound toxic elements in the southeast coastland of China - Shui-Ping Wu; Xiang Li; Mei-Jun Cai; Yang Gao; Chao Xu; James J. Schwab; Chung-Shin Yuan (Environmental Science and Pollution Research, 2021)

A new ent -kaurane diterpene from Isodon henryi - Xue Jiang; Ling-Xia Zhang; Qing-Mei Feng; Hong Wu; Ya-Lin Liu; De-Qin Wang; Li-Ping Dai; Zhi-Min Wang (Natural Product Research, 2021)

Estimation of mountain block recharge on the northern Tianshan Mountains using numerical modeling - Jian-hua Ping; Ya-qiang Zhu; Xue-mei Mei; Wei Leng; Sheng Li; Ji-chang Zhao (Journal of Mountain Science, 2021)

Proton Pump Inhibitor Exposure and Acute Myocardial Infarction Risk: A Nested Cohort Study - Hsiang-Jung Tseng; Chih-Ming Cheng; Shih-Jen Tsai; Wei-Chen Lin; Ya-Mei Bai; Chia-Fen Tsai; Tung-Ping Su; Cheng-Ta Li; Tzeng-Ji Chen; Mu-Hong Chen (Cardiovascular Toxicology, 2021)

LAI scale effect research based on compact airborne spectrographic imager data in the Heihe Oasis - Xiao-ai Dai; Chao Liu; Nai-wen Li; Mei-lian Wang; Yu-wei Yang; Xing-ping Yang; Shi-qi Zhang; Xu-wei He; Zheng-li Yang; Heng Lu; Jing-zhong Li; Ze-kun Wang (Journal of Mountain Science, 2021)

Nutrigenomics reveals potential genetic underpinning of diverse taste preference of Chinese men - Zhouhai Zhu; Junpu Mei; Silong Sun; Sheming Lu; Meng Li; Ying Guan; Ying Chen; Yuqiong Xu; Tao Zhang; Fengxue Shi; Xuemei Li; Mingming Miao; et al. (Genes & Genomics, 2021)

Effect of fermentation bed on bacterial growth in the fermentation mattress material and cecum of ducks - Jian- mei Wang; Xin- meng Gan; Fa-jun Pu; Wan- xia Wang; Min Ma; Ling-li Sun; Ji-wei Hu; Bo Hu; Rong-ping Zhang; Li-li Bai; Liang Li; He-he Liu (Archives of Microbiology, 2021)

Influence of major water conservation projects on river channels and shorelines in the middle and lower reaches of the Yangtze River - Yue-hua Jiang; He-qin Cheng; Quan-ping Zhou; Yun Li; Guo-qiang Yang; Yang Jin; Shi-jia Mei; Xuan Gu; Hong Zhang (Arabian Journal of Geosciences, 2021)

Sesquiterpenoids from the roots and rhizomes of Valeriana amurensis and their effects on NGF-induced neurite outgrowth in PC12 cells - Fa-Wu Dong; Fang Li; Jia-Jia Ren; Cheng-Mei Zhao; Hong-Li Diao; Bao-Jing Li; Yan-Ping Li; Jiang-Miao Hu; Hong-Ping He (Natural Product Research, 2021)

Interest-activity symptom severity predicts response to ketamine infusion in treatment-resistant depression - Mu-Hong Chen; Wei-Chen Lin; Hui-Ju Wu; Ya-Mei Bai; Cheng-Ta Li; Shih-Jen Tsai; Chen-Jee Hong; Pei-Chi Tu; Tung-Ping Su (Psychopharmacology, 2021)

Lentibacillus saliphilus. sp. nov., a moderately halophilic bacterium isolated from a saltern in Korea - Yun Wang; Gang-Qiang Jiang; Hong-Ping Lin; Peng Sun; Hong-Yan Zhang; Dong-Mei Lu; Li-Yun Wang; Chang-Jin Kim; Shu-Kun Tang (Archives of Microbiology, 2021)

Sesquiterpenoids and meroterpenoids from a mangrove derived fungus Diaporthe sp. SCSIO 41011 - Xiao-Wei Luo; Chun-Mei Chen; Kun-Long Li; Xiu-Ping Lin; Cheng-Hai Gao; Xue-Feng Zhou; Yong-Hong Liu (Natural Product Research, 2021)

Flavonoids as key bioactive components of Oxytropis falcata bunge, a traditional anti-inflammatory and analgesic Tibetan medicine - Mei-Rong Zhang; Kan Jiang; Jun-Li Yang; Yan-Ping Shi (Natural Product Research, 2020)

NAC103, a NAC family transcription factor, regulates ABA response during seed germination and seedling growth in Arabidopsis - Ling Sun; Li-Ping Liu; Ya-Zhen Wang; Lei Yang; Mei-Jing Wang; Jian-Xiang Liu (Planta, 2020)

Larger regional volume of the thalamus in diarrhea-predominant irritable bowel syndrome: a cross-sectional study - Cui Ping Mao; Fen Rong Chen; Hong Hong Sun; Mei Juan Shi; Hua Juan Yang; Xiao Hui Li; Dun Ding (Brain Imaging and Behavior, 2020)

Comparing GWAS and Brain Structure-Specific Gene Expression Profiles Identifies Psychiatric Disorder-Related Brain Structures at Different Developmental Stages - Xin Qi; Cuiyan Wu; Yanan Du; Shiqiang Cheng; Yan Wen; Mei Ma; Chujun Liang; Li Liu; Bolun Cheng; Lu Zhang; Ping Li; Feng Zhang (Neuroscience Bulletin, 2020)

Vitamin D receptor gene methylation in patients with hand, foot, and mouth disease caused by enterovirus 71 - Ya-Ping Li; Hui-Ling Deng; Wen-Jun Wang; Mu-Qi Wang; Mei Li; Yu-Feng Zhang; Jun Wang; Shuang-Suo Dang (Archives of Virology, 2020)

Reclassification of Brevibacterium frigoritolerans DSM 8801T as Bacillus frigoritolerans comb. nov. Based on Genome Analysis - Guo-Hong Liu; Bo Liu; Jie-Ping Wang; Jian-Mei Che; Peng-Fei Li (Current Microbiology, 2020)

High throughput solid-phase screening of bacteria with cyclic amino alcohol deamination activity for enantioselective synthesis of chiral cyclic β-amino alcohols - Ya-Wen Chang; Jian-Dong Zhang; Xiao-Xiao Yang; Jing Li; Li-Li Gao; Shuang-Ping Huang; Xing-Mei Guo; Cao-Feng Zhang; Hong-Hong Chang; Jian-He Xu (Biotechnology Letters, 2020)

Detection of serum IgM and IgG for COVID-19 diagnosis - Ling Zhong; Junlan Chuan; Bo Gong; Ping Shuai; Yu Zhou; Yi Zhang; Zhilin Jiang; Dingding Zhang; Xiaoqi Liu; Shi Ma; Yi Huang; He Lin; et al. (Science China Life Sciences, 2020)

Evaluating the Genetic Correlations Between Left-Handedness and Mental Disorder Using Linkage Disequilibrium Score Regression and Transcriptome-Wide Association Study - Bolun Cheng; Chujun Liang; Ping Li; Li Liu; Shiqiang Cheng; Mei Ma; Lu Zhang; Xin Qi; Yan Wen; Feng Zhang (Biochemical Genetics, 2020)

Enhanced adsorption of hydrophobic organic contaminants by high surface area porous graphene - Lixuan Ma; Kai Li; Chi Wang; Bo Liu; Hongbo Peng; Yi Mei; Ping Ning (Environmental Science and Pollution Research, 2020)

Microbial methane production is affected by secondary metabolites in the heartwood of living trees in upland forests - Huan-Long Li; Xi-Mei Zhang; Feng-Dan Deng; Xing-Guo Han; Chun-Wang Xiao; Shi-Jie Han; Zhi-Ping Wang (Trees, 2020)

Effects of root exudates on the activation and remediation of cadmium ion in contaminated soils - Cheng Chen; Zhongbao Li; Shengjin Li; Nanxin Deng; Ping Mei (Environmental Science and Pollution Research, 2020)

Genome-based reclassification of Bacillus plakortidis Borchert et al. 2007 and Bacillus lehensis Ghosh et al. 2007 as a later heterotypic synonym of Bacillus oshimensis Yumoto et al. 2005; Bacillus rhizosphaerae Madhaiyan et al. 2011 as a later heterotypic synonym of Bacillus clausii Nielsen et al. 1995 - Guo-Hong Liu; Manik Prabhu Narsing Rao; Zhou-Yan Dong; Jie-Ping Wang; Jian-Mei Che; Qian-Qian Chen; Cetin Sengonca; Bo Liu; Wen-Jun Li (Antonie van Leeuwenhoek, 2019)

The Verticillium dahliae Sho1‐MAPK pathway regulates melanin biosynthesis and is required for cotton infection - Jun‐Jiao Li; Lei Zhou; Chun‐Mei Yin; Dan‐Dan Zhang; Steven J. Klosterman; Bao‐Li Wang; Jian Song; Dan Wang; Xiao‐Ping Hu; Krishna V. Subbarao; Jie‐Yin Chen; Xiao‐Feng Dai (Environmental Microbiology, 2019)
Summary Verticillium dahliae is a soil‐borne fungus that causes vascular wilt on numerous plants worldwide. The fungus survives in the soil for up to 14 years by producing melanized microsclerotia. The protective function of melanin in abiotic stresses is well documented. Here, we found that the V . dahliae tetraspan transmembrane protein VdSho1, a homolog of the Saccharomyces cerevisiae Sho1, acts as an osmosensor, and is required for plant penetration and melanin biosynthesis. The deletion mutant Δ Sho1 was incubated on a cellophane membrane substrate that mimics the plant epidermis, revealing that the penetration of Δ Sho1 strain was reduced compared to the wild‐type strain. Furthermore, VdSho1 regulates melanin biosynthesis by a signalling mechanism requiring a kinase‐kinase signalling module of Vst50‐Vst11‐Vst7. Strains, Δ Vst50 , Δ Vst7 and Δ Vst11 also displayed defective penetration and melanin production like the Δ Sho1 strain. Defects in penetration and melanin production in Δ Sho1 were restored by overexpression of Vst50 , suggesting that Vst50 lies downstream of VdSho1 in the regulatory pathway governing penetration and melanin biosynthesis. Data analyses revealed that the transmembrane portion of VdSho1 was essential for both membrane penetration and melanin production. This study demonstrates that Vst50‐Vst11‐Vst7 module regulates VdSho1‐mediated plant penetration and melanin production in V . dahliae , contributing to virulence.

Combined gastroscopic and choledochoscopic transabdominal nasobiliary drainage - Song-mei Lou; Min Zhang; Zheng-rong Wu; Gui-xing Jiang; Hua Shen; Yi Dai; Yue-long Liang; Li-ping Cao; Guo-ping Ding (Journal of Zhejiang University-SCIENCE B, 2019)

Three new labdane-type diterpenoids from Callicarpa macrophylla Vahl. - Zhen-Hui Wang; Huan-Jun Xu; Yang-Yang Zhai; Lan-Ping Yang; Qiang Li; Mei Huang; Xing-Ying Chen; Wen-Kui Zhang; Yue-Li Meng; Qing-Ling Zhang; Chao Niu; Yan-Ru Zhang (Natural Product Research, 2019)

A new abietane diterpenoid glycoside from ajuga ovalifolia var. calantha - Fan Yang; Hong-Ping Chen; Xiao-Fei Shen; Hu-Lan Chen; Yin Chen; Li-Xia Wang; Hai Zhang; Wen-Ji Zhao; Mei Zhang; Yu-Zhu Tan (Natural Product Research, 2019)

Recent research progress in geochemical properties and restoration of heavy metals in contaminated soil by phytoremediation - Jiang-tao Fu; Dong-mei Yu; Xi Chen; Ying Su; Cai-hong Li; Yong-ping Wei (Journal of Mountain Science, 2019)

A novel astrovirus identified in wild rhesus monkey feces in China - Yun-yun Xin; Li-li Li; Yuan-yun Ao; Zhi-ping Xie; Jin-song Li; Zhao-jun Duan; Jie-mei Yu; Bing Zhang (Archives of Virology, 2019)

Favus of Scrotum Due to Trichophyton rubrum in Immunocompetent Patients: A Clinical, Mycological and Ultrastructural Study - Ze-Hu Liu; Xiu-Jiao Xia; Yong Zhang; Yan Zhong; Bo Sang; Qiu-Ping Li; Mei Wang; Wen-Wen Lv; Hui-Lin Zhi; Xiang-Dong Wang; Cui-Ping Guan; Hong Shen (Mycopathologia, 2019)

Expression of the intrarenal angiotensin receptor and the role of renin-angiotensin system inhibitors in IgA nephropathy - Zheng Zhang; Shi-min Jiang; Ye-ping Ma; Pei-lin Dai; Yi-ning Wang; Gu-ming Zou; Hong-mei Gao; Yue Yang; Wen-ge Li (Molecular and Cellular Biochemistry, 2019)

Antioxidant and α -glucosidase inhibitory ingredients identified from Jerusalem artichoke flowers - Yan-Ming Wang; Jian-Qiang Zhao; Jun-Li Yang; Pema Tsering Idong; Li-Juan Mei; Yan-Duo Tao; Yan-Ping Shi (Natural Product Research, 2019)

Luminescence chronology of the Palaeolithic–Neolithic transition in the Yujiagou site at the Nihewan Basin, northern China - Xue Rui; Yu‐Jie Guo; Jia‐Fu Zhang; Yue Hu; Hui‐Jie Mei; You‐Ping Wang; Fei Xie; Bo Li (Journal of Quaternary Science, 2019)
The relationship between the Palaeolithic–Neolithic cultural transition and environmental changes is important for understanding human history. However, the timing and nature of human behaviour at the transition, and their relationship to local environmental conditions, remain poorly understood. The Yujiagou archaeological site in the Nihewan Basin, northern China, provides valuable chronological and archaeological information about cultural changes in northern China due to its continuous archaeological sequence of cultural layers from the Palaeolithic to Neolithic. In this study, we apply post‐infrared infrared stimulated luminescence (pIRIR) dating on individual feldspar grains to date the Yujiagou deposits. We provide a revised chronology for the archaeological sequence at the site. We combine these results with multi‐proxy climatic indicators to gain insights into palaeoenvironmental changes in the region. The results show that the age of the artefact‐bearing deposits ranges from 13.5 to 9.7 ka. Polished stones and pottery begin to occur in the archaeological layer around 13 ka, corresponding to a transitional period when the local climate changed from cold to warm. This site provides evidence for understanding the process that led to the regional transition from hunter‐gathering to farming.

Transcriptome Reveals Differentially Expressed Genes in Saccharum spontaneum GX83-10 Leaf Under Drought Stress - Kai-Chao Wu; Li-Ping Wei; Cheng-Mei Huang; Yuan-Wen Wei; Hui-Qing Cao; Lin Xu; Hai-Bin Luo; Sheng-Li Jiang; Zhi-Nian Deng; Yang-Rui Li (Sugar Tech, 2018)

miR-377-3p regulates adipogenic differentiation of human bone marrow mesenchymal stem cells by regulating LIFR - Xingnuan Li; Yaofang Yang; Ruiqiao Yan; Xiaoyuan Xu; Liyun Gao; Jun Mei; Jianyun Liu; Xinping Wang; Jie Zhang; Ping Wu; Weidong Li; Zhijun Zhao; et al. (Molecular and Cellular Biochemistry, 2018)

Molecular and Functional Characterization of ZmNF-YC14 in Transgenic Arabidopsis - Xiupeng Mei; Ping Li; Lu Wang; Chaoxian Liu; Lian Zhou; Yilin Cai (Journal of Plant Biology, 2018)

Lycium barbarum polysaccharide attenuates diabetic testicular dysfunction via inhibition of the PI3K/Akt pathway-mediated abnormal autophagy in male mice - Guang-Jiang Shi; Jie Zheng; Xiao-Xu Han; Ya-Ping Jiang; Zhi-Mei Li; Jing Wu; Qing Chang; Yang Niu; Tao Sun; Yu-Xiang Li; Zhen Chen; Jian-Qiang Yu (Cell and Tissue Research, 2018)

Low-Cd tomato cultivars (Solanum lycopersicum L.) screened in non-saline soils also accumulated low Cd, Zn, and Cu in heavy metal-polluted saline soils - Zhi-Min Xu; Xiao-Qi Tan; Xiu-Qin Mei; Qu-Sheng Li; Chu Zhou; Li-Li Wang; Han-Jie Ye; Ping Yang (Environmental Science and Pollution Research, 2018)

Ascorbic acid inhibits cadmium-induced disruption of the blood-testis barrier by regulating oxidative stress-mediated p38 MAPK pathways - Na Chen; Ping Su; Mei Wang; Ya-Min Li (Environmental Science and Pollution Research, 2018)

Genomic and Transcriptomic Analysis Identified Gene Clusters and Candidate Genes for Oil Content in Peanut (Arachis hypogaea L.) - Xiaohua Wang; Ping Xu; Liang Yin; Yan Ren; Shuangling Li; Yanmao Shi; Thomas D. Alcock; Qing Xiong; Wei Qian; Xiaoyuan Chi; Manish K. Pandey; Rajeev K. Varshney; et al. (Plant Molecular Biology Reporter, 2018)

Effect of UGT2B7 genotypes on plasma concentration of valproic acid: a meta-analysis - Ping Wang; Xiao-Qian Lin; Wen-Ke Cai; Gui-Li Xu; Meng-Di Zhou; Mei Yang; Gong-Hao He (European Journal of Clinical Pharmacology, 2018)

Epidemiology and clinical characteristics of human coronaviruses OC43, 229E, NL63, and HKU1: a study of hospitalized children with acute respiratory tract infection in Guangzhou, China - Zhi-Qi Zeng; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Huan-Xi Liang; Mei-Xin Chen; Xiao Li; Zheng-Shi Lin; Wen-Kuan Liu; Rong Zhou (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

C21 steroid derivatives from the Dai herbal medicine Dai-Bai-Jie, the dried roots of Marsdenia tenacissima, and their screening for anti-HIV activity - Xu Pang; Li-Ping Kang; Xiao-Mei Fang; He-Shui Yu; Li-Feng Han; Yang Zhao; Li-Xia Zhang; Li-Yan Yu; Bai-Ping Ma (Journal of Natural Medicines, 2018)

Structural features and proto-type basin reconstructions of the Bay of Bengal Basin: A remnant ocean basin model - Peng Zhang; Lianfu Mei; Ping Xiong; Xiaolin Hu; Renyuan Li; Huaning Qiu (Journal of Earth Science, 2017)

Environmental change and raw material selection strategies at Taoshan: a terminal Late Pleistocene to Holocene site in north‐eastern China - Shi‐Xia Yang; Yu‐Xiu Zhang; You‐Qian Li; Chao Zhao; Xiao‐Qiang Li; Jian‐Ping Yue; Ya‐Mei Hou; Cheng‐Long Deng; Ri‐Xiang Zhu; Michael D. Petraglia (Journal of Quaternary Science, 2017)
The Lesser Khingan Mountains of north‐eastern China are heavily forested, making archaeological site identification difficult owing to poor ground surface visibility. Nevertheless, several prehistoric archaeological site discoveries have been made in recent years and a limited number of excavations have been initiated. One of the most important sites to emerge is Taoshan, which has yielded stratified stone tool assemblages dating from the Last Glacial Maximum (LGM) to the mid‐Holocene. Pollen profiles indicate significant changes in vegetation, fluctuating from steppe conditions during the LGM to forested conditions in the Bølling–Allerød interstadial (B–A) and the mid‐Holocene. The stone tool assemblages from Taoshan were primarily produced from varieties of volcanic tuff, rhyolite, hornfels and agate. Geological prospecting and petrological analyses were performed to document procurement sources and changes in raw material exploitation strategies. During the LGM, the predominant raw material was vitric tuff, available from a source ca. 5–10 km from Taoshan. In the B–A and mid‐Holocene layers, emphasis was on the exploitation of raw materials in gravel bars, although stone tool reduction techniques and raw material preferences changed considerably during this time interval. Diachronic changes in raw materials and exploitation strategies correspond to changes in vegetation and human adaptations.

Separation of antioxidant and α -glucosidase inhibitory flavonoids from the aerial parts of Asterothamnus centrali - asiaticus - Yan-Ming Wang; Jian-Qiang Zhao; Jun-Li Yang; Yan-Duo Tao; Li-Juan Mei; Yan-Ping Shi (Natural Product Research, 2017)

Epigenetic Downregulation of Scn3a Expression by Valproate: a Possible Role in Its Anticonvulsant Activity - Na-Na Tan; Hui-Ling Tang; Guo-Wang Lin; Yong-Hong Chen; Ping Lu; Hai-Jun Li; Mei-Mei Gao; Qi-Hua Zhao; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Molecular Neurobiology, 2017)

Novel compound heterozygous mutations in ZAP70 in a Chinese patient with leaky severe combined immunodeficiency disorder - Qing Liu; Yan-Ping Wang; Qiao Liu; Qin Zhao; Xue-Mei Chen; Xiu-Hong Xue; Li-Na Zhou; Yuan Ding; Xue-Mei Tang; Xiao-Dong Zhao; Zhi-Yong Zhang (Immunogenetics, 2017)

Morphological and molecular characterization of the second backcross progenies of Ogu-CMS Chinese kale and rapeseed - Hai-long Yu; Zhi-yuan Li; Li-mei Yang; Yu-mei Liu; Mu Zhuang; Lu-gang Zhang; Hong-hao Lv; Zhan-sheng Li; Feng-qing Han; Xiao-ping Liu; Zhi-yuan Fang; Yang-yong Zhang (Euphytica, 2017)

Size Effects on the Interaction of QDs with the Mitochondrial Membrane In Vitro - Lu Lai; Ya-Ping Li; Ping Mei; Wu Chen; Feng-Lei Jiang; Yi Liu (The Journal of Membrane Biology, 2016)

RhoB/ROCK mediates oxygen–glucose deprivation-stimulated syncytiotrophoblast microparticle shedding in preeclampsia - Jian Han; Bo-ping Yang; Yi-lin Li; Hong-mei Li; Xiu-hui Zheng; Li-li Yu; Qiong Zhang; Ying-ru Zheng; Ping Yi; Li Li; Jian-xin Guo; Yuan-guo Zhou (Cell and Tissue Research, 2016)

Proteomic Analyses for the Global S-Nitrosylated Proteins in the Brain Tissues of Different Human Prion Diseases - Li-Na Chen; Qi Shi; Bao-Yun Zhang; Xiao-Mei Zhang; Jing Wang; Kang Xiao; Yan Lv; Jing Sun; Xiao-Dong Yang; Cao Chen; Wei Zhou; Jun Han; et al. (Molecular Neurobiology, 2016)

Polymorphisms in complement genes and risk of preeclampsia in Taiyuan, China - Weiwei Wu; Hailan Yang; Yongliang Feng; Ping Zhang; Shuzhen Li; Xin Wang; Tingting Peng; Fang Wang; Bingjie Xie; Pengge Guo; Mei Li; Ying Wang; et al. (Inflammation Research, 2016)

Synergistic antitumor activity of triple-regulated oncolytic adenovirus with VSTM1 and daunorubicin in leukemic cells - Jiao Zhou; Qiu-Mei Yao; Jin-Lan Li; Yan Chang; Ting Li; Wen-Ling Han; Hong-Ping Wu; Lin-Fang Li; Qi-Jun Qian; Guo-Rui Ruan (Apoptosis, 2016)

A new isocoumarin from the aerial parts of Aconitum gymnandrum - Jian-Qiang Zhao; Yan-Ming Wang; Shuo Wang; Jun Dang; Yan-Ping Shi; Li-Juan Mei; Yan-Duo Tao (Natural Product Research, 2016)

Development of a novel allele-specific Rfo marker and creation of Ogura CMS fertility-restored interspecific hybrids in Brassica oleracea - Hai-long Yu; Zhi-yuan Fang; Yu-mei Liu; Li-mei Yang; Mu Zhuang; Hong-hao Lv; Zhan-sheng Li; Feng-qing Han; Xiao-ping Liu; Yang-yong Zhang (Theoretical and Applied Genetics, 2016)

Comparative genomic analysis of Lactobacillus plantarum ZJ316 reveals its genetic adaptation and potential probiotic profiles - Ping Li; Xuan Li; Qing Gu; Xiu-yu Lou; Xiao-mei Zhang; Da-feng Song; Chen Zhang (Journal of Zhejiang University-SCIENCE B, 2016)

Emerging role of adipokines in systemic lupus erythematosus - Hong-Miao Li; Tian-Ping Zhang; Rui-Xue Leng; Xiang-Pei Li; Xiao-Mei Li; Hai-Rong Liu; Dong-Qing Ye; Hai-Feng Pan (Immunologic Research, 2016)

Interaction between STAT3 gene polymorphisms and smoking on Crohn’s disease susceptibility: a case–control study in a Chinese Han population - Jun-hong Li; Ning Wu; Hong-mei Yang; Hong-bing Tang; Dong-ping Bao; Jun-min Ji (Inflammation Research, 2016)

The Effects of Molecular Properties on Ready Biodegradation of Aromatic Compounds in the OECD 301B CO2 Evolution Test - Mei He; Cheng-Fang Mei; Guo-Ping Sun; Hai-Bei Li; Lei Liu; Mei-Ying Xu (Archives of Environmental Contamination and Toxicology, 2016)

Calcitriol regulates angiotensin-converting enzyme and angiotensin converting-enzyme 2 in diabetic kidney disease - Mei Lin; Ping Gao; Tianya Zhao; Lei He; Mengshi Li; Yaoyao Li; Hua Shui; Xiaoyan Wu (Molecular Biology Reports, 2016)

Calpain-Dependent ErbB4 Cleavage Is Involved in Brain Ischemia-Induced Neuronal Death - Ying-mei Lu; Yin-ping Gao; Rong-rong Tao; Mei-hua Liao; Ji-yun Huang; Gang Wu; Feng Han; Xiao-ming Li (Molecular Neurobiology, 2016)

Genetic polymorphism analyses of a novel panel of 19 X-STR loci in the Chinese Uygur ethnic minority - Yu-xin Guo; Jian-gang Chen; Yan Wang; Jiang-wei Yan; Jing Chen; Tian-hua Yao; Li-ping Zhang; Guang Yang; Hao-tian Meng; Yu-dang Zhang; Ting Mei; Yao-shun Liu; et al. (Journal of Zhejiang University-SCIENCE B, 2016)

Development and Psychometric Testing Chinese Version of the Frommelt Attitude Toward Care of the Dying Scale, Form B in Nurses and Nursing Students - Li-Ping Wang; Ya-Jie Li; Wen-Zhen Yan; Guan-Mei Li (Journal of Cancer Education, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Chemical composition, antioxidant and antimicrobial activity of the essential oil from the leaves of Macleaya cordata (Willd) R. Br. - Chun-Mei Li; Xiao-Yong Yang; Yi-Rong Zhong; Jian-Ping Yu (Natural Product Research, 2016)

Combination of Estrogen and Immunosuppressive Agents to Establish a Mouse Model of Candidiasis with Concurrent Oral and Vaginal Mucosal Infection - Le Wang; Chong Wang; Huan Mei; Yongnian Shen; Guixia Lv; Rong Zeng; Ping Zhan; Dongmei Li; Weida Liu (Mycopathologia, 2016)

Effect of fish oil supplement in maintenance hemodialysis patients: a systematic review and meta-analysis of published randomized controlled trials - Lei He; Meng-si Li; Mei Lin; Tian-ya Zhao; Ping Gao (European Journal of Clinical Pharmacology, 2016)

Effects of freshwater leaching on potential bioavailability of heavy metals in tidal flat soils - Hui Li; Jun Lu; Qu-Sheng Li; Bao-Yan He; Xiu-Qin Mei; Dan-Ping Yu; Zhi-Min Xu; Shi-Hong Guo; Hui-Jun Chen (Environmental Geochemistry and Health, 2016)

Molecular and pathogenicity characterization of Gallid herpesvirus 2 newly isolated in China from 2009 to 2013 - Yan-ping Zhang; Hong-chao Lv; Ke-yan Bao; Yu-long Gao; Hong-lei Gao; Xiao- le Qi; Hong-yu Cui; Yong-qiang Wang; Kai Li; Li Gao; Xiao-mei Wang; Chang-jun Liu (Virus Genes, 2016)

Dissimilarity of phytoplankton assemblages in two connected tropical reservoirs: effects of water transportation and environmental filtering - Li-Juan Xiao; Ren Hu; Liang Peng; La-Mei Lei; Yu Feng; Bo-Ping Han (Hydrobiologia, 2016)

Differential effects of general anesthetics on anxiety-like behavior in formalin-induced pain: involvement of ERK activation in the anterior cingulate cortex - Cong Luo; Yan-Ling Zhang; Wei Luo; Fiona H Zhou; Chang-Qi Li; Jun-Mei Xu; Ru-Ping Dai (Psychopharmacology, 2015)

The role of KCa3.1 channels in cardiac fibrosis induced by pressure overload in rats - Li-Mei Zhao; Li-Ping Wang; Hui-Fang Wang; Xiao-Zhen Ma; Dang-Xia Zhou; Xiu-Ling Deng (Pflügers Archiv - European Journal of Physiology, 2015)

Rice grassy stunt virus nonstructural protein p5 serves as a viral suppressor of RNA silencing and interacts with nonstructural protein p3 - Chao Zhang; Xiao-juan Liu; Kang-cheng Wu; Lu-Ping Zheng; Zuo-mei Ding; Fei Li; Peng Zou; Liang Yang; Jian-guo Wu; Zu-jian Wu (Archives of Virology, 2015)

p55γ functional mimetic peptide N24 blocks vascular proliferative disorders - Jiaojiao Guo; Ning Xie; Geng Li; Yan Zhang; Fengxiang Lv; Sile Guo; Yuanqing Feng; Chun-Mei Cao; Rui-Ping Xiao (Journal of Molecular Medicine, 2015)

Up-regulation of SPOCK1 induces epithelial–mesenchymal transition and promotes migration and invasion in esophageal squamous cell carcinoma - Xiaopeng Song; Ping Han; Jingmei Liu; Yunwu Wang; Dongxiao Li; Jiayi He; Jin Gong; Mengke Li; Wei Tu; Wei Yan; Mei Liu; Huanjun Huang; et al. (Journal of Molecular Histology, 2015)

The miR-573/apoM/Bcl2A1-dependent signal transduction pathway is essential for hepatocyte apoptosis and hepatocarcinogenesis - Yan-Wei Hu; Zhi-Ping Chen; Xiu-Mei Hu; Jia-Yi Zhao; Jin-Lan Huang; Xin Ma; Shu-Fen Li; Yu-Rong Qiu; Xiao-Juan Wu; Yan-Hua Sha; Ji-Juan Gao; Yan-Chao Wang; et al. (Apoptosis, 2015)

Endoplasmic Reticulum Protein 29 Protects Axotomized Neurons from Apoptosis and Promotes Neuronal Regeneration Associated with Erk Signal - Yun-Hui Zhang; Visar Belegu; Yu Zou; Fang Wang; Bao-Jiang Qian; Ran Liu; Ping Dai; Wei Zhao; Fa-Bao Gao; Lei Wang; Li-Mei Cao; John W. McDonald; et al. (Molecular Neurobiology, 2015)

Activation of VEGF/Flk-1-ERK Pathway Induced Blood–Brain Barrier Injury After Microwave Exposure - Li-Feng Wang; Xiang Li; Ya-Bing Gao; Shui-Ming Wang; Li Zhao; Ji Dong; Bin-Wei Yao; Xin-Ping Xu; Gong-Min Chang; Hong-Mei Zhou; Xiang-Jun Hu; Rui-Yun Peng (Molecular Neurobiology, 2015)

Effects of Fluoride on DNA Damage and Caspase-Mediated Apoptosis in the Liver of Rats - Guo Hua Song; Fu Bing Huang; Ji Ping Gao; Mao Lin Liu; Wen Biao Pang; Wei bin Li; Xiao Yan Yan; Mei Jun Huo; Xia Yang (Biological Trace Element Research, 2015)

Marker-assisted breeding for transgressive seed protein content in soybean [Glycine max (L.) Merr.] - Ying Hu Zhang; Mei Feng Liu; Jian Bo He; Yu Feng Wang; Guang Nan Xing; Yan Li; Shou Ping Yang; Tuan Jie Zhao; Jun Yi Gai (Theoretical and Applied Genetics, 2015)

West Eurasian mtDNA lineages in India: an insight into the spread of the Dravidian language and the origins of the caste system - Malliya Gounder Palanichamy; Bikash Mitra; Cai-Ling Zhang; Monojit Debnath; Gui-Mei Li; Hua-Wei Wang; Suraksha Agrawal; Tapas Kumar Chaudhuri; Ya-Ping Zhang (Human Genetics, 2015)

A Novel Oral Preparation of Hydroxysafflor Yellow A Base on a Chitosan Complex: A Strategy to Enhance the Oral Bioavailability - Guan-nan Ma; Fang-lin Yu; Shan Wang; Zhi-ping Li; Xiang-yang Xie; Xing-guo Mei (AAPS PharmSciTech, 2015)

Ectopic expression of a phytochrome B gene from Chinese cabbage (Brassica rapa L. ssp. pekinensis) in Arabidopsis thaliana promotes seedling de-etiolation, dwarfing in mature plants, and delayed flowering - Mei-Fang Song; Shu Zhang; Pei Hou; Hong-Zhong Shang; Hai-Ke Gu; Jing-Juan Li; Yang Xiao; Lin Guo; Liang Su; Jian-Wei Gao; Jian-Ping Yang (Plant Molecular Biology, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Genome-wide discovery of novel and conserved microRNAs in white shrimp (Litopenaeus vannamei) - Qian-Yun Xi; Yuan-Yan Xiong; Yuan-Mei Wang; Xiao Cheng; Qi-En Qi; Gang Shu; Song-Bo Wang; Li-Na Wang; Ping Gao; Xiao-Tong Zhu; Qing-Yan Jiang; Yong-Liang Zhang; et al. (Molecular Biology Reports, 2015)

Upregulation of HIF-1α Via Activation of ERK and PI3K Pathway Mediated Protective Response to Microwave-Induced Mitochondrial Injury in Neuron-Like Cells - Li Zhao; Yue-Feng Yang; Ya-Bing Gao; Shui-Ming Wang; Li-Feng Wang; Hong-Yan Zuo; Ji Dong; Xin-Ping Xu; Zhen-Tao Su; Hong-Mei Zhou; Ling-Ling Zhu; Rui-Yun Peng (Molecular Neurobiology, 2014)

Potent in vitro synergism of fusidic acid (FA) and berberine chloride (BBR) against clinical isolates of methicillin-resistant Staphylococcus aureus (MRSA) - Rong-mei Liang; Xiao-lan Yong; Yu-qin Duan; Yong-hong Tan; Ping Zeng; Zi-ying Zhou; Yan Jiang; Shi-hua Wang; Yun-ping Jiang; Xiao-chun Huang; Zhao-hui Dong; Ting-ting Hu; et al. (World Journal of Microbiology and Biotechnology, 2014)

Regulatory control of carotenoid accumulation in winter squash during storage - Ming Ke Zhang; Mei Ping Zhang; Michael Mazourek; Yaakov Tadmor; Li Li (Planta, 2014)

A new epimer of ocotillol from stems and leaves of American ginseng - Liu Han; Mei-Yu Lin; Qian Zheng; Hai-Yu Liu; Hai-Yan Liu; Gang Dong; Jin-Ping Liu; Ping-Ya Li (Natural Product Research, 2014)

Sequence and phylogenetic analysis of surface protein genes of emerging H9N2 influenza viruses isolated from poultry in two geographical regions of China - Yu Xue; Jing-Lan Wang; Zhuan-Qiang Yan; Guang-Wei Li; Shun-Yan Chen; Xiang-Bin Zhang; Jian-Ping Qin; Hai-Yan Li; Shuang Chang; Feng Chen; Ying-Zuo Bee; Qing-Mei Xie (Virus Genes, 2014)

Over-expression of heat shock factor gene (AtHsfA1d) from Arabidopsis thaliana confers formaldehyde tolerance in tobacco - Hong-Juan Nian; Dao-Jun Zhang; Zhi-Dong Zeng; Jin-Ping Yan; Kun-Zhi Li; Li-Mei Chen (Acta Physiologiae Plantarum, 2014)

Identification of BACH2 as a susceptibility gene for Graves’ disease in the Chinese Han population based on a three-stage genome-wide association study - Wei Liu; Hai-Ning Wang; Zhao-Hui Gu; Shao-Ying Yang; Xiao-Ping Ye; Chun-Ming Pan; Shuang-Xia Zhao; Li-Qiong Xue; Hui-Jun Xie; Sha-Sha Yu; Cui-Cui Guo; Wen-Hua Du; et al. (Human Genetics, 2014)

A dwarfing mutant caused by deactivation function of alpha subunit of the heterotrimeric G-protein in rice - De-wei Yang; Xiang-hua Zheng; Chao-ping Cheng; Wen-da Wang; Deng-hui Xing; Li-bin Lu; Chen-de Liu; Ning Ye; Mei-juan Zeng; Xin-fu Ye (Euphytica, 2014)

Geochronology and geochemistry of the Late Triassic Longtan pluton in South China: termination of the crustal melting and Indosinian orogenesis - Liang Qiu; Dan-Ping Yan; Mei-Fu Zhou; Nicholas T. Arndt; Shuang-Li Tang; Liang Qi (International Journal of Earth Sciences, 2014)

Exposure to diethylhexyl phthalate (DEHP) results in a heritable modification of imprint genes DNA methylation in mouse oocytes - Lan Li; Teng Zhang; Xun-Si Qin; Wei Ge; Hua-Gang Ma; Li-Lan Sun; Zhu-Mei Hou; Hong Chen; Ping Chen; Guo-Qing Qin; Wei Shen; Xi-Feng Zhang (Molecular Biology Reports, 2014)

Advanced glycation end products impair KCa3.1- and KCa2.3-mediated vasodilatation via oxidative stress in rat mesenteric arteries - Li-Mei Zhao; Yan Wang; Xiao-Zhen Ma; Nan-Ping Wang; Xiu-Ling Deng (Pflügers Archiv - European Journal of Physiology, 2014)

Further studies on Toxascaris leonina (Linstow, 1902) (Ascaridida: Ascarididae) from Felis lynx (Linnaeus) and Panthera leo (Linnaeus) (Carnivora: Felidae) - Li-Mei Xue; Jing-Bo Chai; Yan-Ning Guo; Lu-Ping Zhang; Liang Li (Acta Parasitologica, 2014)
Toxascaris leonina (Linstow, 1902) is a most common intestinal parasite of various animals in Felidae and Canidae. In the present paper, light and scanning electron microscopy (SEM) were used to study the morphological aspects of adult worms of this nematode in detail, based on the material collected from Panthera leo (Linnaeus) and Felis lynx (Linnaeus) (Carnivora: Felidae) in China. The results showed that there were some morphometric differences between the present material and the previous studies, including the body size, the width and length of cervical alae, the number of denticles on each lip and the tail length of the female. Previously unreported morphological features were also revealed. These supplementary morphological and morphometric data contributed to a more accurate identification of this worldwide distributed ascarid nematode.

ROCK is Involved in Vimentin Phosphorylation and Rearrangement Induced by Dengue Virus - Shun Lei; Yan-Ping Tian; Wei-Dong Xiao; Shu Li; Xian-Cai Rao; Jun-Lei Zhang; Jie Yang; Xiao-Mei Hu; Wei Chen (Cell Biochemistry and Biophysics, 2013)

The Characterization of Childhood Occipital Epilepsy of Gastaut: A Study of Seven Patients - Xiao Mei Shu; Gui Ping Zhang; Bing Zhu Yang; Juan Li (Cell Biochemistry and Biophysics, 2013)

Interaction Between AT1 Receptor and NF-κB in Hypothalamic Paraventricular Nucleus Contributes to Oxidative Stress and Sympathoexcitation by Modulating Neurotransmitters in Heart Failure - Xiao-Jing Yu; Yu-Ping Suo; Jie Qi; Qing Yang; Hui-Hua Li; Dong-Mei Zhang; Qiu-Yue Yi; Jian Zhang; Guo-Qing Zhu; Zhiming Zhu; Yu-Ming Kang (Cardiovascular Toxicology, 2013)

Influence of serum adiponectin level and SNP +45 polymorphism of adiponectin gene on myocardial fibrosis - Cheng-jun Yan; Su-mei Li; Qiang Xiao; Yan Liu; Jian Hou; Ai-fang Chen; Li-ping Xia; Xiu-chang Li (Journal of Zhejiang University-SCIENCE B, 2013)

Continuous evolution of avian infectious bronchitis virus resulting in different variants co-circulating in southern China - Meng Li; Mei-Lan Mo; Bai-Cheng Huang; Wen-Sheng Fan; Zheng-Ji Wei; Tian-Chao Wei; Kang-Ran Li; Ping Wei (Archives of Virology, 2013)

A consensus envelope protein domain III can induce neutralizing antibody responses against serotype 2 of dengue virus in non-human primates - Hsin-Wei Chen; Shih-Jen Liu; Yi-Shiuan Li; Hsueh-Hung Liu; Jy-Ping Tsai; Chen-Yi Chiang; Mei-Yu Chen; Chyi-Sing Hwang; Chin-Cheng Huang; Hui-Mei Hu; Han-Hsuan Chung; Sze-Hsien Wu; et al. (Archives of Virology, 2013)

Molecular characterization and phylogenetic analysis of infectious bursal disease viruses isolated from chicken in South China in 2011 - Di Liu; Xiang-Bin Zhang; Zhuan-Qiang Yan; Feng Chen; Jun Ji; Jian-Ping Qin; Hai-Yan Li; Jun-Peng Lu; Yu Xue; Jia-Jia Liu; Qing-Mei Xie; Jing-Yun Ma; et al. (Tropical Animal Health and Production, 2013)

Overexpression of MsALMT1, from the Aluminum-Sensitive Medicago sativa, Enhances Malate Exudation and Aluminum Resistance in Tobacco - Qi Chen; Kong-Huan Wu; Ping Wang; Jia Yi; Kun-Zhi Li; Yong-Xiong Yu; Li-Mei Chen (Plant Molecular Biology Reporter, 2013)

Expression of yeast acyl-CoA-∆9 desaturase leads to accumulation of unusual monounsaturated fatty acids in soybean seeds - Jin-Ai Xue; Xue Mao; Zhi-Rong Yang; Yong-Mei Wu; Xiao-Yun Jia; Li Zhang; Ai-Qin Yue; Ji-Ping Wang; Run-Zhi Li (Biotechnology Letters, 2013)

Arbuscular mycorrhizal symbiosis and active ingredients of medicinal plants: current research status and prospectives - Yan Zeng; Lan-Ping Guo; Bao-Dong Chen; Zhi-Peng Hao; Ji-Yong Wang; Lu-Qi Huang; Guang Yang; Xiu-Ming Cui; Li Yang; Zhao-Xiang Wu; Mei-Lan Chen; Yan Zhang (Mycorrhiza, 2013)

Paracoccus siganidrum sp. nov., isolated from fish gastrointestinal tract - Ying Liu; Qing-yi Xie; Kui Hong; Lei Li; Ya-mei Zhao; Yi-li Tang; Jun-ying An; Ping-ping Zhu; Chun-hou Xu (Antonie van Leeuwenhoek, 2013)

Ventral medial prefrontal functional connectivity and emotion regulation in chronic schizophrenia: A pilot study - Feng-Mei Fan; Shu-Ping Tan; Fu-De Yang; Yun-Long Tan; Yan-Li Zhao; Nan Chen; Bin-Bin Li; Chong-Sheng Song; Yun-Hui Wang; Zhen Jin; Dong-Feng Zhou; Michael P. Milham; et al. (Neuroscience Bulletin, 2013)

Fluid evolution of the Jiawula Ag–Pb–Zn deposit, Inner Mongolia: mineralogical, fluid inclusion, and stable isotopic evidence - De-Gao Zhai; Jia-Jun Liu; Jian-Ping Wang; Mei-Juan Yao; Sheng-Hua Wu; Chao Fu; Zhen-Jiang Liu; Shou-Guang Wang; Yu-Xi Li (International Geology Review, 2013)

Involvement of antioxidant defense system in chill hardening-induced chilling tolerance in Jatropha curcas seedlings - Ping-Xing Ao; Zhong-Guang Li; Dong-Mei Fan; Ming Gong (Acta Physiologiae Plantarum, 2013)

Biomass accumulation and partitioning, photosynthesis, and photosynthetic induction in field-grown maize (Zea mays L.) under low- and high-nitrogen conditions - Jun-Wen Chen; Zhi-Qing Yang; Ping Zhou; Mei-Rong Hai; Tian-Xiang Tang; Yan-Li Liang; Tong-Xin An (Acta Physiologiae Plantarum, 2013)

Advanced glycation end products promote proliferation of cardiac fibroblasts by upregulation of KCa3.1 channels - Li-Mei Zhao; Wei Zhang; Li-Ping Wang; Gui-Rong Li; Xiu-Ling Deng (Pflügers Archiv - European Journal of Physiology, 2012)

Genome characterization of a novel porcine bocavirus - Wan-zhu Yang; Jie-mei Yu; Jin-song Li; Wei-xia Cheng; Can-ping Huang; Zhao-jun Duan (Archives of Virology, 2012)

Neuroprotective properties of aucubin in diabetic rats and diabetic encephalopathy rats - Hong Yu Xue; Ya Nan Lu; Xue Mei Fang; Yong Ping Xu; Gui Zhen Gao; Li Ji Jin (Molecular Biology Reports, 2012)

Genome-wide Identification and Characterization of a Dehydrin Gene Family in Poplar (Populus trichocarpa) - Chang-Cai Liu; Chun-Ming Li; Bao-Guang Liu; Su-Jie Ge; Xiu-Mei Dong; Wei Li; Hang-Yong Zhu; Bai-Chen Wang; Chuan-Ping Yang (Plant Molecular Biology Reporter, 2012)

Pseudolaric acid B-driven phosphorylation of c-Jun impairs its role in stabilizing HIF-1alpha: a novel function-converter model - Bing Yu; Mei-Hong Li; Wei Wang; Ying-Qing Wang; Yi Jiang; Sheng-Ping Yang; Jian-Min Yue; Jian Ding; Ze-Hong Miao (Journal of Molecular Medicine, 2012)

Response to weaning and dietary l-glutamine supplementation: metabolomic analysis in piglets by gas chromatography/mass spectrometry - Ying-ping Xiao; Tian-xing Wu; Qi-hua Hong; Jiang-ming Sun; An-guo Chen; Cai-mei Yang; Xiao-yan Li (Journal of Zhejiang University-SCIENCE B, 2012)

Risk stratification of spontaneous bacterial peritonitis in cirrhosis with ascites based on classification and regression tree analysis - Ke-Qing Shi; Yu-Chen Fan; Li Ying; Xian-Feng Lin; Mei Song; Ling-Fei Li; Xie-Yan Yu; Yong-Ping Chen; Ming-Hua Zheng (Molecular Biology Reports, 2012)

C/EBP-α ameliorates CCl4-induced liver fibrosis in mice through promoting apoptosis of hepatic stellate cells with little apoptotic effect on hepatocytes in vitro and in vivo - Li-Li Tao; Yuan-Yuan Cheng; Di Ding; Shuang Mei; Jia-Wen Xu; Juan Yu; Qi Ou-Yang; Long Deng; Qi Chen; Qing-Quan Li; Zu-De Xu; Xiu-Ping Liu (Apoptosis, 2012)

Genetic Overlap in the Quantitative Resistance of Rice at the Seedling and Adult Stages to Xanthomonas oryzae pv. oryzae - Yong-Li Zhou; Xue-Wen Xie; Mei-Rong Xu; Jin-Ping Zang; Ling-Hua Zhu; Jian-Long Xu; Zhi-Kang Li (Journal of Plant Biology, 2012)

Genetic polymorphism analysis of killer cell immunoglobulin-like receptor genes in the Chinese Uygur population - Hong-dan Wang; Bo-feng Zhu; Chun-mei Shen; Guo-lian Yuan; Guang Yang; Juan-ning Guo; Jiang-wei Yan; Hai-xia Qin; Jian-xin Guo; Li-ping Zhang; Xiao-qin Jia; Rudolf Lucas (Molecular Biology Reports, 2012)

Inhibition of ROS-activated ERK1/2 pathway contributes to the protection of H2S against chemical hypoxia-induced injury in H9c2 cells - Xiao-Bian Dong; Chun-Tao Yang; Dong-Dan Zheng; Li-Qiu Mo; Xiu-Yu Wang; Ai-Ping Lan; Fen Hu; Pei-Xi Chen; Jian-Qiang Feng; Mei-Fen Zhang; Xin-Xue Liao (Molecular and Cellular Biochemistry, 2012)

Phylogenetic relationships of Chinese Adiantum based on five plastid markers - Jin-Mei Lu; Jun Wen; Sue Lutz; Yi-Ping Wang; De-Zhu Li (Journal of Plant Research, 2012)

Serotype and genotype diversity of infectious bronchitis viruses isolated during 1985-2008 in Guangxi, China - Meng Li; Xiu-Ying Wang; Ping Wei; Qiu-Ying Chen; Zheng-Ji Wei; Mei-Lan Mo (Archives of Virology, 2012)

Central nervous system regulation of food intake and energy expenditure: role of galanin-mediated feeding behavior - Peng-Hua Fang; Mei Yu; Yin-Ping Ma; Jian Li; Yu-Mei Sui; Ming-Yi Shi (Neuroscience Bulletin, 2011)

Facial dermatosis associated with Demodex: a case-control study - Ya-e Zhao; Yan Peng; Xiang-lan Wang; Li-ping Wu; Mei Wang; Hu-ling Yan; Sheng-xiang Xiao (Journal of Zhejiang University-SCIENCE B, 2011)

Human amniotic fluid-derived stem cells can differentiate into hepatocyte-like cells in vitro and in vivo - Hui Liu; Da-qing Liu; Bao-wei Li; Li-dong Guan; Zhi-feng Yan; Ya-li Li; Xue-tao Pei; Wen Yue; Min Wang; Yan-ping Lu; Hong-mei Peng; Yang Lv (In Vitro Cellular & Developmental Biology - Animal, 2011)

Detection of hepatitis C virus by an improved loop-mediated isothermal amplification assay - Jin Yang; Mei-xin Fang; Jie Li; Guo-qiang Lou; Hang-jun Lu; Nan-ping Wu (Archives of Virology, 2011)

A systemic proteomic analysis of Populus chloroplast by using shotgun method - Hong-Mei Yuan; Kai-Long Li; Rui-Juan Ni; Wen-Dong Guo; Zhuo Shen; Chuan-Ping Yang; Bai-Chen Wang; Gui-Feng Liu; Chang-Hong Guo; Jing Jiang (Molecular Biology Reports, 2011)

Effects of the crude extract of Polygala tenuifolia Willd on human sperm in vitro - Yi Qiu; Lei-guang Wang; Yi-fang Jia; Dan-tong Yang; Mei-hua Zhang; Yan-ping Zhang; Li-hong Zhang; Ling Gai (Journal of Zhejiang University-SCIENCE B, 2011)

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability - Jun Ge; Ben-Xu Tan; Ye Chen; Li Yang; Xing-Chen Peng; Hong-Ze Li; Hong-Jun Lin; Yu Zhao; Meng Wei; Ke Cheng; Long-Hao Li; Hang Dong; et al. (Journal of Molecular Medicine, 2011)

Protection of CHO cells by transfer of survivin driven by ovarian-specific promoter OSP-2 - Chun-Hua Tu; Wei-Peng Liu; Mei Dong; Li-Ping Cai; Ya-Qin Mo; Dong-Zi Yang (Molecular Biology Reports, 2011)

Determination of Trace Deoxyribonucleic Acid by Using Fluorescein Isothiocyanate-Phenosafranine as a Double-Luminescent Phosphorescence Probe - Jia-Ming Liu; Xiao-Mei Huang; Zhen-Bo Liu; Fei-Ming Li; Li-Ping Lin; Xin-Xing Wang; Chang-Qing Lin; Ya-Hong Huang; Zhi-Ming Li; Shao-Qin Lin (Journal of Fluorescence, 2011)

Population genetic analysis of 15 autosomal STR loci in the Russian population of northeastern Inner-Mongolia, China - Bo-feng Zhu; Guang Yang; Chun-mei Shen; Hai-xia Qin; Shuan-liang Fan; Li-bin Deng; Feng Chen; Li-ping Chen; Hong-dan Wang; Zhen-yuan Wang; Rudolf Lucas; Zhen-min Lian (Molecular Biology Reports, 2010)

FLT3 and NPM1 mutations in Chinese patients with acute myeloid leukemia and normal cytogenetics - Lei Wang; Wei-lai Xu; Hai-tao Meng; Wen-bin Qian; Wen-yuan Mai; Hong-yan Tong; Li-ping Mao; Yin Tong; Jie-jing Qian; Yin-jun Lou; Zhi-mei Chen; Yun-gui Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2010)

Genetic evolution of equine influenza viruses isolated in China - Ting Qi; Wei Guo; Wen-Qiang Huang; Hong-Mei Li; Li-Ping Zhao; Ling-Li Dai; Na He; Xiao-Fang Hao; Wen-Hua Xiang (Archives of Virology, 2010)

Sensitive Phosphorimetric Determination of Bumetanide in Human Urine with Its Inhibition Effect on the Formation of [Fe-morin] 3+ Complex - Li-Qing Zeng; Jia-Ming Liu; Fei-Ming Li; Xiao-Mei Huang; Li-Ping Lin; Xin-Xing Wang; Li-Hong Zhang; Chang-Qing Lin (Journal of Fluorescence, 2010)

Improvement of heat and drought photosynthetic tolerance in wheat by overaccumulation of glycinebetaine - Gui-Ping Wang; Zhen Hui; Feng Li; Mei-Rong Zhao; Jin Zhang; Wei Wang (Plant Biotechnology Reports, 2010)

The efficacy of FMD vaccine reduced non-structural proteins with a mAb against 3B protein - Dong Li; Zai-Xin Liu; Pu Sun; Yong-Liang Li; Zeng-Jun Lu; Mei-Na Tian; Ying-Li Chen; Bao-Xia Xie; Hui-Fang Bao; Yuan-Fang Fu; Yi-Mei Cao; Ping-Hua Li; et al. (Veterinary Research Communications, 2010)

Association Analysis of the RET Proto-Oncogene with Hirschsprung Disease in the Han Chinese Population of Southeastern China - Cui-Ping Liu; Qian-Qian Tang; Jin-Tu Lou; Chun-Fen Luo; Xue-Wu Zhou; Dong-Mei Li; Fei Chen; Xiang Li; Ji-Cheng Li (Biochemical Genetics, 2010)

Synthesis and evaluation of antiinflammatory activity of substituted chalcone derivatives - Xue-Wu Zhang; Dong-Hai Zhao; Ying-Chun Quan; Liang-Peng Sun; Xiu-Mei Yin; Li-Ping Guan (Medicinal Chemistry Research, 2010)

Effects of Ginkgo biloba extracts on diazepam metabolism: a pharmacokinetic study in healthy Chinese male subjects - Xiao-Cong Zuo; Bi-Kui Zhang; Su-Jie Jia; Shi-Kun Liu; Ling-Yun Zhou; Jing Li; Jie Zhang; Ling-Ling Dai; Ben-Mei Chen; Guo-Ping Yang; Hong Yuan (European Journal of Clinical Pharmacology, 2010)

Treatment strategies for Parkinson’s disease - Hong Yuan; Zhen-Wen Zhang; Li-Wu Liang; Quan Shen; Xiang-Dang Wang; Su-Mei Ren; Hong-Jie Ma; Shu-Jun Jiao; Ping Liu (Neuroscience Bulletin, 2010)

Distributions of HLA-A and -B alleles and haplotypes in the Yi ethnic minority of Yunnan, China: relationship to other populations - Bo-feng Zhu; Guang Yang; Chun-mei Shen; Hai-xia Qin; Shun-zhi Liu; Ya-jun Deng; Shuan-liang Fan; Li-bin Deng; Feng Chen; Ping Zhang; Jie Fang; Li-ping Chen; et al. (Journal of Zhejiang University-SCIENCE B, 2010)

RNA interference effectively degrades mRNA and inhibits protein expression of GBV-C E2 gene in Huh7 cells - Ming-Mei Cao; Gang Li; Hao Ren; Wei Pan; Ping Zhao; Zhong-Tian Qi (Virus Genes, 2009)

Inhibitory effect of reinioside C on monocyte–endothelial cell adhesion induced by oxidized low-density lipoprotein via inhibiting NADPH oxidase/ROS/NF-κB pathway - Yong-Ping Bai; Chang-ping Hu; Mei-Fang Chen; Kang-Ping Xu; Gui-Shan Tan; Rui-Zhen Shi; Yuan-Jian Li; Guo-Gang Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Selection of housekeeping genes for gene expression studies on the development of fruit bearing shoots in Chinese jujube (Ziziphus jujube Mill.) - Hai-feng Sun; Yu-ping Meng; Gui-mei Cui; Qiu-fen Cao; Jie Li; Ai-hua Liang (Molecular Biology Reports, 2009)

Manganese-induced changes of the biochemical characteristics of the recombinant wild-type and mutant PrPs - Xiao-Li Li; Chen-Fang Dong; Gui-Rong Wang; Rui-Min Zhou; Qi Shi; Chan Tian; Chen Gao; Guo-Yong Mei; Cao Chen; Kun Xu; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2009)

Human papillomavirus type-distribution in cervical cancer in China: the importance of HPV 16 and 18 - Wen Chen; Xun Zhang; Anco Molijn; David Jenkins; Ju-Fang Shi; Wim Quint; Johannes E. Schmidt; Ping Wang; Yu-Ling Liu; Lian-Kun Li; Hong Shi; Ji-Hong Liu; et al. (Cancer Causes & Control, 2009)

Prevalence of human metapneumovirus in hospitalized children with respiratory tract infections in Tianjin, China - Xiao-yan Li; Jin-ying Chen; Mei Kong; Xu Su; Yan-ping Yi; Ming Zou; Hua Zhang (Archives of Virology, 2009)

Blockade of HERG K+ channel by isoquinoline alkaloid neferine in the stable transfected HEK293 cells - Dong-fang Gu; Xue-lian Li; Zhi-ping Qi; Sha-shan Shi; Mei-qin Hu; Dong-min Liu; Cheng-bai She; Yan-jie Lv; Bao-xin Li; Bao-feng Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Memory deficits and neurochemical changes induced by C-reactive protein in rats: implication in Alzheimer’s disease - Huan-Bing Lin; Xue-Mei Yang; Tie-Jun Li; Yu-Fang Cheng; Han-Ting Zhang; Jiang-Ping Xu (Psychopharmacology, 2009)

Antimicrobial activity of isolate HL-12 against Clavibacter michiganensis subsp. michiganensis in the presence of cadmium - Hai-ping Yuan; Hang Min; Zhen-mei Lv; Zi-mu Li (Ecotoxicology, 2009)

Quantification of Three Key Enzymes Involved in Artemisinin Biogenesis in Artemisia annua by Polyclonal Antisera-Based ELISA - Qing-Ping Zeng; Xiao-Mei Zeng; Lu-Lu Yin; Rui-Yi Yang; Li-Ling Feng; Xue-Qin Yang (Plant Molecular Biology Reporter, 2009)

Distribution and Accumulation of Copper and Cadmium in Soil–Rice System as Affected by Soil Amendments - Ping Li; Xing-xiang Wang; Tao-lin Zhang; Dong-mei Zhou; Yuan-qiu He (Water, Air, & Soil Pollution, 2009)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Crossover randomized controlled trial of the electronic version of the Chinese SF-36 - Tian-hui Chen; Lu Li; Joerg M. Sigle; Ya-ping Du; Hong-mei Wang; Jun Lei (Journal of Zhejiang University-SCIENCE B, 2007)

Determination of Trace Mercury by Solid Substrate-Room Temperature Phosphorimetry Quenching Method Based on Catalytic Effect of Hg2+on Formation of the Ion Association Complex [Sn(XO)6]4+·[(Fin)4] - Jia-Ming Liu; Ruo-Hong Wu; De-Chang Li; Ping Zhou; Min-Min Zheng; Xiao-Yi Zeng; Dong-Xia Liu; Xiao-Mei Huang; Guo-Hui Zhu (Journal of Fluorescence, 2006)

Synthesis of Site-Specifically Dimethylated and Trimethylated Peptides Derived from Histone H3 N-Terminal Tail - Zhi-Ping Huang; Jin-Tang Du; Yu-Fen Zhao; Yan-Mei Li (International Journal of Peptide Research and Therapeutics, 2006)

Studies on the Interaction of Tricyclazole with β-cyclodextrin and human Serum Albumin by Spectroscopy - Hua-Xin Zhang; Xing Huang; Ping Mei; Ke-Hua Li; Cheng-Nong Yan (Journal of Fluorescence, 2006)

Fog- and Rainwater Chemistry in the Tropical Seasonal Rain Forest of Xishuangbanna, Southwest China - Wen Jie Liu; Yi Ping Zhang; Hong Mei Li; Fan Rui Meng; Yu Hong Liu; Chang-Ming Wang (Water, Air, & Soil Pollution, 2005)

Fast screening target sites for RNA interference using a cell-free system - Huang Mei; Jia Fang-Jun; Li Chong-Yong; Li Yi-Ping; Guo Li-He (Biotechnology Letters, 2005)

Minimizing phenol pollution in sugarcane stem apical meristem culture - Cheng-Mei Huang; Yang-Rui Li; Yan-Ping Ye (Sugar Tech, 2003)

Crystal structure studies on rubrerythrin: enzymatic activity in relation to the zinc movement - Mei Li; Ming-yih Liu; Jean LeGall; Lu-lu Gui; Jun Liao; Tao Jiang; Ji-ping Zhang; Dong-cai Liang; Wen-rui Chang (JBIC Journal of Biological Inorganic Chemistry, 2003)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)